Ionic Polymer Composition

JP7637396B2Active Publication Date: 2025-02-28HYALEX ORTHOPAEDICS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024152952
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-01-11
Filing Date
2024-09-05
Publication Date
2025-02-28
Estimated Expiration
2039-07-17

Smart Images

  • Figure 0007637396000013
    Figure 0007637396000013
  • Figure 0007637396000014
    Figure 0007637396000014
  • Figure 0007637396000015
    Figure 0007637396000015
Patent Text Reader

Abstract

To provide ionic polymer compositions containing semi- and fully interpenetrating polymer networks, a method of making such ionic polymer compositions, articles made from such ionic polymer compositions, and a method of making such articles and packaging for such articles.SOLUTION: Implant includes an interpenetrating polymer network structure or semi-interpenetrating polymer network structure which include a first polymer network structure containing first polymer and a second polymer network structure containing ionic polymers.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a continuation-in-part of U.S. Application No. 16 / 246,292, entitled "Ionic Polymer Compositions," filed January 11, 2019, and claims the benefit of U.S. Application No. 62 / 699,497, entitled "Ionic Polymer Compositions," filed July 17, 2018. The disclosures of each prior application are hereby incorporated by reference in their entirety.

[0002] The present disclosure relates to ionic polymer compositions comprising semi- and fully interpenetrating polymer networks, methods of making such ionic polymer compositions, articles made from such ionic polymer compositions, and methods of making and packaging such articles. [Background technology]

[0003] Full interpenetrating polymer networks (IPNs) and semi-interpenetrating polymer networks ("semi-IPNs") have been made from a variety of starting materials and used in a variety of applications. IPNs and semi-IPNs can combine the advantageous properties of each of their starting polymers.

[0004] IPNs and semi-IPNs for biomedical applications are described, for example, in U.S. Patent Publication No. 2009 / 0008846, U.S. Patent Publication No. 2013 / 0096691, U.S. Patent Publication No. 2017 / 0107370, U.S. Patent Publication No. 2012 / 0045651, U.S. Patent Publication No. 2012 / 0209396, U.S. Patent Publication No. 2017 / 0327624, U.S. Patent Publication No. 2013 / 0131741, and WO2017 / 027590. Summary of the Invention

[0005] For purposes herein, a "carboxylic acid group" can refer to both the non-ionized (protonated) and ionized (carboxylate) forms of the group. For purposes herein, a "sulfonic acid group" can refer to both the non-ionized (protonated) and ionized (sulfonate) forms of the group.

[0006] For the purposes of this application, an "interpenetrating polymer network" or "IPN" is a material that includes two or more polymer networks that are at least partially interlocked at the molecular level, but are not covalently bonded to each other and cannot be separated unless chemical bonds are broken. A "semi-interpenetrating polymer network" or "semi-IPN" is a material that includes one or more polymer networks and one or more linear or branched polymers, characterized in that at least one network is perforated at the molecular level by at least some linear or branched macromolecules. Semi-interpenetrating polymer networks are distinguished from interpenetrating polymer networks because the constituent linear or branched polymers can in principle be separated from the constituent polymer networks without breaking chemical bonds; these are polymer blends.

[0007] A "polymer" is a material that includes macromolecules, including homopolymers (polymers derived from one type of monomer) and copolymers (polymers derived from multiple types of monomers). A "hydrophobic polymer" is a preformed polymer network that has at least one of the following two characteristics: (1) a surface water contact angle of at least 45°, and (2) a water absorption rate of 2.5% or less after 24 hours at room temperature according to ASTM test standard D570. A "hydrophilic polymer" is a polymer network that has a surface water contact angle of less than 45° and a water absorption rate of more than 2.5% after 24 hours at room temperature according to ASTM test standard D570. An "ionic polymer" is defined as a polymer that is composed of ionic monomers (e.g., monomers having carboxylate groups, sulfonate groups, or both), ionizable monomers (e.g., monomers having protonated carboxyl groups, protonated sulfonate groups, or both), or both ionic and ionizable monomers, but typically contains at least 2% by weight of ionic or ionizable monomers (or both), regardless of their nature and location. A "thermosetting polymer" is one that, unlike a thermoplastic polymer, does not melt when heated. Thermosetting polymers are "set" into a given shape when first made and do not flow or melt later, but rather decompose when heated and are often highly and / or covalently crosslinked. A "thermoplastic polymer" is one that, unlike a thermosetting polymer, melts or flows when heated. Thermoplastic polymers are usually not covalently crosslinked. "Phase separation" is defined as the transformation of a single-phase system to a multiphase system, specifically the separation of two immiscible blocks of a block copolymer into two phases (there may be a small interphase that results in slight intermixing).

[0008] In certain aspects, the present disclosure relates to ionic polymers that include a combination of carboxylic acid groups and sulfonic acid groups. In certain of these aspects, the present disclosure relates to ionic polymers that include a combination of underivatized groups and sulfonic acid derivatized groups.

[0009] In certain aspects, the present disclosure relates to ionic polymers that include a combination of underivatized carboxylic acid groups and sulfonic acid derivatized groups, including aminosulfonic acid derivatized carboxylic acid groups.

[0010] In certain embodiments, the sulfonic acid derivatized groups are present only on the surface of the ionic polymer. In certain embodiments, the sulfonic acid derivatized groups may extend from the surface of the ionic polymer into the bulk of the ionic polymer for a distance of at least 10 microns, at least 50 microns, at least 100 microns, at least 250 microns, at least 500 microns, at least 1000 microns, at least 2500 microns, or at least 5000 microns, at least 10000 microns or more, for example, from 0 microns to 10 microns, 25 microns, 50 microns, 100 microns, 250 microns, 500 microns, 1000 microns, 2500 microns, 5000 microns, 10000 microns or more.

[0011] In certain embodiments, at least 1%, at least 5%, at least 10%, at least 15%, at least 20%, at least 25%, at least 50%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95% or the entire thickness of the ionic polymer has sulfonic acid derivatized groups.

[0012] In certain embodiments, the sulfonic acid derivatized groups extend from the surface of the ionic polymer into the bulk of the ionic polymer and are present in detectable amounts up to a distance from the surface of at least 250 microns, at least 500 microns, at least 1000 microns, at least 2500 microns, at least 5000 microns, or at least 10000 microns or more, e.g., are present in detectable amounts at distances from the surface ranging from 250 microns to 500 microns, 1000 microns, 2500 microns, 5000 microns, 10000 microns or more.

[0013] In certain of these embodiments, the concentration of sulfonic acid derivatized groups in the ionic polymer decreases to 50% or more from the surface up to a distance of at least 100 microns, at least 250 microns, at least 500 microns, at least 1000 microns, at least 2500 microns, at least 5000 microns, at least 10000 microns or more.

[0014] In certain embodiments, the concentration of sulfonic acid derivatized groups in the ionic polymer at a depth of 100 microns may range from 0% to 5%, 10%, 25%, 50%, 75%, 90%, 95%, 100% of the surface concentration of sulfonic acid derivatized groups.

[0015] In certain embodiments, the ionic polymers described herein, including all of the ionic polymers described above, can have a thickness ranging from about 2 mm to 3 mm, 4 mm, 5 mm, 7.5 mm, 10 mm or more.

[0016] In certain embodiments, the present disclosure relates to interpenetrating and semi-interpenetrating polymer networks comprising the ionic polymers described herein, including all of the ionic polymers described above. Such interpenetrating and semi-interpenetrating polymer networks can have thicknesses ranging from, for example, about 2 mm to 3 mm, 4 mm, 5 mm, 7.5 mm, 10 mm or more.

[0017] In certain aspects, the present disclosure relates to methods of forming the ionic polymers described herein and interpenetrating polymer networks and semi-interpenetrating polymer networks comprising the ionic polymers described herein.

[0018] In certain aspects, the present disclosure relates to implants, including orthopedic implants formed from the ionic polymers described herein and from interpenetrating polymer networks and semi-interpenetrating polymer networks comprising the ionic polymers described herein.

[0019] In certain aspects, the present disclosure relates to packaged articles of manufacture containing implants, including orthopedic implants formed from the ionic polymers described herein and from interpenetrating polymer networks and semi-interpenetrating polymer networks comprising the ionic polymers described herein.

[0020] In various embodiments, the implant is at least partially immersed in a divalent cation-containing solution that includes water and one or more divalent metal cations. The divalent cation-containing solution may be, for example, a simulated body fluid that contains physiological levels of ions present in body fluids such as synovial fluid or serum or cerebrospinal fluid. In certain embodiments, the divalent cation-containing solution may include 0.1-5 mM total divalent metal cations. The concentration of total divalent cations in a solution is the combined concentration of all divalent cations in the solution (e.g., if 1 liter of solution contains 0.5 millimoles of calcium cations and 0.5 millimoles of magnesium cations and no other divalent cations, the solution contains 1.0 mM total divalent cations). In certain embodiments, the divalent cation-containing solution may include calcium ions, magnesium ions, or a combination of calcium ions and magnesium ions. For example, the divalent cation-containing solution may contain 0.5-5.0 mM calcium ion, typically 0.5-2.0 mM calcium ion, more typically 0.8-1.6 mM calcium ion, and in some embodiments 1.1-1.3 mM calcium ion, among other possibilities, and / or the divalent cation-containing solution may contain 0.2-1.5 mM magnesium ion, typically 0.3-1.0 mM magnesium ion, and in some embodiments 0.5-0.7 mM magnesium ion, among other possibilities. In certain embodiments, the divalent cation-containing solution may further contain a monovalent metal ion selected from sodium ion, potassium ion, or a combination of sodium ion and potassium ion, in which case the divalent cation-containing solution may contain 0-300 mM total monovalent metal cations, among other possibilities. In various embodiments, the ionic polymer comprises carboxylic acid groups, sulfonic acid groups, or a combination of carboxylic acid groups and sulfonic acid groups, as described elsewhere herein.

[0021] In various embodiments, the implant comprises an interpenetrating polymer network or a semi-interpenetrating polymer network comprising a first polymer and a second polymer network comprising an ionic polymer as described elsewhere herein.

[0022] In various embodiments, the implant may be selected as a hip implant, knee implant, shoulder implant, hand implant, toe implant, or any site within the body where cartilage is desired to be replaced as described elsewhere herein. In some embodiments, the implant is adapted to repair or replace cartilage in a joint within the body, such as, for example, the knee joint, condyle, patella, tibial plateau, ankle joint, elbow joint, shoulder joint, finger joint, thumb joint, glenoid cavity, hip joint, intervertebral disc, facet joint, labrum, meniscus, metacarpal joint, metatarsal joint, toe joint, temporomandibular joint, or wrist joint, and any site thereof.

[0023] In certain aspects, the present disclosure relates to orthopedic implants, including those described elsewhere herein, that maintain their dimensions and mechanical properties under bivalent conditions.

[0024] In certain aspects, the present disclosure relates to orthopedic implants, including those described elsewhere herein, that maintain water content over the physiological range of divalent ion concentrations present in a living organism, particularly a mammal, and more particularly a human, such as synovial fluid (i.e., within a range of ±5 wt%, preferably ±2 wt%, more preferably ±1 wt%).

[0025] In certain embodiments, the present disclosure demonstrates an absolute % weight change of less than 10%, less than 5%, less than 3%, less than 2%, or even less than 1% (ideally demonstrating no measurable weight change) per mM change in total divalent cation concentration, e.g., 1.4 mM (0.96 mM Ca 2+ , 0.48 mM Mg 2+ ) to a high physiological divalent cation level of 2.2 mM (1.44 mM Ca 2+ , 0.72 mM Mg 2+The present invention relates to orthopedic implants, including those described elsewhere herein, that demonstrate such properties for total divalent cation concentrations ranging from about 0.1 mM to about 5 mM, including total divalent cation concentrations ranging from about 0.1 mM to about 5 mM.

[0026] In certain embodiments, the present disclosure provides a method for treating a pulmonary artery disease comprising administering to a subject a therapeutically effective amount of about 1.4 mM (0.96 mM Ca 2+ , 0.48 mM Mg 2+ ) to approximately 2.2 mM (1.44 mM Ca 2+ , 0.72 mM Mg 2+ The present invention relates to orthopedic implants, including those described elsewhere herein, which maintain a coefficient of friction of less than 0.1, preferably less than 0.075, and more preferably less than 0.05 over a range of total divalent cation concentrations from about 0.1 mM to about 5 mM, including the range of physiological total divalent cation concentrations of 0.1 mM to about 5 mM.

[0027] The present disclosure includes methods for modifying commonly available hydrophobic thermosetting or thermoplastic polymers, such as polyurethane or acrylonitrile butadiene styrene (ABS), to produce new materials with novel properties, such as improved strength, lubricity, electrical conductivity, and wear resistance. Various hydrophobic thermosetting or thermoplastic polymers are described below. The present disclosure also includes IPN and semi-IPN compositions and articles made from such compositions and methods of using such articles. The IPN and semi-IPN compositions of the present disclosure may achieve one or more of the following characteristics: high tensile and compressive strength, low coefficient of friction, high water content and swelling, high permeability, biocompatibility, and biostability.

[0028] Applications of the present disclosure include making hydrophilic lubricant articles and coatings to reduce the static and dynamic coefficient of friction between two bearing surfaces and to reduce the formation of biofilms and / or barnacles in ships, other vessels or waterborne objects, or in conduits. Applications of the present disclosure further include electrochemical applications requiring the conduction of electric current or the permeation of ions, such as proton exchange membranes, fuel cells, filtration devices, and ion exchange membranes. In addition, the present disclosure can be used as a method for manufacturing bearing components and moving parts for applications such as engines, pistons, or other machines or machine parts. The present disclosure can also be used in numerous biomedical applications, including cartilage replacement, orthopedic joint replacement and resurfacing devices or components thereof, intervertebral discs, stents, vascular or urinary catheters, condoms, heart valves, vascular implants, and both short-term and long-term implants in other areas of the body, such as the skin, brain, spine, gastrointestinal system, larynx, and soft tissues in general. In addition, the present disclosure can be used as a component of various surgical tools and instruments. In various applications, drugs can be incorporated into the materials of the present disclosure for localized drug delivery, including drug delivery vehicles in which a therapeutic agent is released from a polymer matrix.

[0029] As previously mentioned, in certain aspects, the present disclosure relates to ionic polymers and methods of forming the same that include a combination of underivatized carboxylic acid groups and sulfonic acid derivatized groups, including aminosulfonic acid derivatized carboxylic acid groups.

[0030] Sulfonic acid functional groups may be incorporated into already formed solid articles (i.e., solid state articles, including porous and nonporous articles) that include a precursor polymer that includes carboxylic acid groups. In some embodiments, sulfonic acid functional groups may be incorporated into already formed IPNs or semi-IPNs (including gradient IPNs or semi-IPNs) that include carboxylic acid groups. The general principle is to replace the carboxylic acid groups present on the poly(carboxylic acid) in the IPN, e.g., poly(acrylic acid) or poly(methacrylic acid), with sulfonic acid-containing functional groups, among other possibilities. In some embodiments, a method is provided that includes reacting (a) a solid article that includes a precursor polymer that includes carboxylic acid groups with (b) a sulfonic acid-containing compound (e.g., by reacting the carboxylic acid group of the solid article with an aminosulfonic acid compound to form an amide bond between the carboxylic acid group of the precursor polymer and the amine group of the aminosulfonic acid compound).

[0031] In certain embodiments, hydrophilic-hydrophobic IPNs containing carboxylic acid groups (e.g., carboxylate ionizable groups), as described in US2013 / 0138210, incorporated herein by reference, can be sulfonated by amidation with an amine-containing sulfonic acid (i.e., aminosulfonic acid). An amide (peptide) bond is formed between the carboxylate of the IPN and the amine in the sulfonic acid.

[0032] In some embodiments, the aminosulfonic acid compound has the formula (HN): x R(SO3H) y (wherein R is an organic moiety, x is a positive integer, and y is a positive integer) or a salt thereof. In certain embodiments, x may range from 1 to 10, typically 1 to 5 (i.e., x may be 1, 2, 3, 4, or 5), and y may range from 1 to 10, typically 1 to 5 (i.e., y may be 1, 2, 3, 4, or 5). In some embodiments, a compound of formula (H2N) x R(SO3H) yThe compound has a hydrodynamic radius that allows for the diffusion of the molecule in the IPN. R may be a hydrocarbon moiety, including, for example, a linear, branched, or cyclic hydrocarbon moiety, or a hydrocarbon moiety having a combination of two or more linear, branched, and cyclic hydrocarbon substituents. The hydrocarbon moiety may be, for example, a C1-C12 hydrocarbon or polymeric moiety (including a polymer / oligomer containing heteroatoms). In certain embodiments, the hydrocarbon moiety may be selected from an alkane moiety, an alkene moiety, an alkyne moiety, an aromatic moiety, or a hydrocarbon moiety having a combination of two or more alkane, alkene, alkyne, or aromatic substituents. In certain embodiments, the aminosulfonic acid is selected from taurine, including 1-substituted, 2-substituted, 1,1-disubstituted, 2,2-disubstituted, and 1,2-disubstituted taurines, such as 1-hydrocarbon substituted, 2-hydrocarbon substituted, 1,1-hydrocarbon-disubstituted, 2,2-hydrocarbon-disubstituted, and 1,2-hydrocarbon-disubstituted taurines;

[0033] [ka] and taurine derivatives, and the substituted hydrocarbon may be selected, for example, from the hydrocarbon moieties described above. In other embodiments, the aminosulfonic acid compound is one that results in the formation of 2-acrylamido-2-methylpropanesulfonic acid or acrylamidoethanesulfonic acid.

[0034] In various embodiments, the method includes contacting a solid article including a precursor polymer having carboxylic acid groups with a sulfonic acid-containing compound such that the sulfonic acid-containing compound (e.g., an aminosulfonic acid compound) diffuses into the solid article.

[0035] In various embodiments, the method further includes contacting the solid article including the precursor polymer having carboxylic acid groups with a coupling reagent to activate the reactive groups (e.g., carboxylic acid groups) in the solid article and promote reaction with the sulfonic acid-containing compound (e.g., by promoting the formation of an amide bond between the carboxylic acid group of the precursor polymer and the amine group of the aminosulfonic acid in the solid article). In these embodiments, the coupling reagent can be diffused into the solid article before the sulfonic acid-containing compound is diffused into the solid article, the coupling reagent can be diffused into the solid article after the sulfonic acid-containing compound is diffused into the solid article, or the coupling reagent and the sulfonic acid-containing compound can be diffused into the solid article simultaneously. Examples of coupling reagents include triazine-based coupling reagents, as well as carbodiimides, phosphonium and aminium salts, organophosphorus reagents, and fluoroformamidinium coupling reagents. In certain embodiments, the coupling reagent may be a carbodiimide coupling reagent selected from 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), 1,3-bis(2,2-dimethyl-1,3-dioxolan-4-ylmethyl)carbodiimide (BDDC), and 1-cyclohexyl-3-[2-morpholinoethyl]carbodiimide. In certain embodiments, the coupling reagent may be a triazine-based coupling agent selected from derivatives of 2,4,6-trichloro-1,3,5-triazine, including 2,4-dichloro-6-methoxy-1,3,5-triazine (DCMT), 2-chloro-4,6-dimethoxy-1,3,5-triazine (CDMT), N-methylmorpholine (NMM), and derivatives thereof with 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM).As discussed in more detail below, Applicants have discovered that by using suitable coupling agents, including triazine-based coupling agents, under suitable conditions, sulfonic acid derivatized groups can be incorporated into solid articles comprising precursor polymers having carboxylic acid groups to depths ranging from a few microns to hundreds of microns, or throughout the entire depth of the material. In various embodiments, the depth to which the sulfonic acid derivatized groups extend can be increased by repeated reactions with sulfonic acid-containing compounds.

[0036] The precursor polymer having carboxylic acid groups may be, for example, a homopolymer or a copolymer (e.g., alternating copolymer, random copolymer, gradient copolymer, block copolymer, etc.) The precursor polymer having carboxylic acid groups may be, for example, selected from polymers comprising one or more monomers selected from acrylic acid, methacrylic acid, crotonic acid, linoleic acid, maleic acid, and fumaric acid, among others.

[0037] In various embodiments, the solid article may include an interpenetrating or semi-interpenetrating polymer network including a first polymer network including a first polymer and a second polymer network including a precursor polymer having carboxylic acid groups. The first polymer may be, for example, a hydrophobic polymer. The first polymer may be, for example, a thermoplastic or thermosetting polymer. In various embodiments described herein, the first polymer may be a hydrophobic thermoplastic or thermosetting polymer. In certain advantageous embodiments, the first polymer may be a hydrophobic thermoplastic polyurethane, such as a particularly hydrophobic thermoplastic polyether urethane.

[0038] In some embodiments, the present disclosure relates to an IPN or semi-IPN (also referred to herein for convenience as a "mixed anionic IPN or semi-IPN") comprising (a) a first polymer network and (b) a second polymer network comprising a crosslinked ionic polymer comprising sulfonic acid derivatized groups. For example, the first polymer may comprise a first polymer described elsewhere herein, and the ionic polymer may comprise a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups. As another example, the first polymer may comprise a first polymer described elsewhere herein, and the ionic polymer may comprise a combination of underivatized carboxylic acid groups, sulfonic acid derivatized carboxylic acid groups, and uncharged groups. As another example, the first polymer may comprise a first polymer described elsewhere herein, and the ionic polymer may comprise a combination of sulfonic acid derivatized carboxylic acid groups, optional uncharged groups, and few or no underivatized carboxylic acid groups (e.g., due to all or essentially all underivatized carboxylic acid groups being converted).

[0039] In some embodiments, the first polymer is a hydrophobic thermosetting or thermoplastic polymer, and the mixed anionic IPN or semi-IPN exhibits a lower coefficient of friction than the hydrophobic thermosetting or thermoplastic polymer. In some embodiments, the mixed anionic IPN or semi-IPN is more water-swellable, more resistant to creep, and / or exhibits higher conductivity and permeability than the hydrophobic thermosetting or thermoplastic polymer. Some embodiments of the composition also include an antioxidant.

[0040] In some embodiments, a mixed anionic IPN or semi-IPN is formed by diffusing monomers, including carboxylic acid group-containing monomers, into a first polymer (e.g., a hydrophobic thermoset or thermoplastic polymer) and polymerizing the monomers to form a precursor polymer that includes carboxylic acid groups. A sulfonic acid-containing compound is subsequently diffused into the IPN or semi-IPN and a portion of the carboxylic acid groups in the precursor polymer are derivatized as described elsewhere herein to produce an ionic polymer that includes a combination of underivatized and sulfonic acid-derivatized carboxylic acid groups. The sulfonic acid-containing compound can be, for example, a carboxylic acid-containing monomer having the formula (H2N) above. x R(SO3H) y The aminosulfonic acid may be of the formula:

[0041] In certain embodiments, the mixed anionic IPN or semi-IPN may contain between 15-40% w / w of ionic polymer, and even more particularly between 25-30% w / w.

[0042] In certain embodiments, of the total amount of underivatized carboxylic acid groups and sulfonate-derivatized carboxylic acid groups in the mixed anionic IPN or semi-IPN (referred to herein as the "total amount"), between 10 and 40 mol %, and even more specifically between 21 and 31 mol %, are sulfonate-derivatized carboxylic acid groups, and between 90 and 60 mol %, and even more specifically between 79 and 69 mol % of the total amount are underivatized carboxylic acid groups.

[0043] In some embodiments, the mixed anionic IPN or semi-IPN also includes water. In certain cases, the water may form a hydration gradient from a first portion of the composition to a second portion of the composition. The electrolyte may be dissolved in water.

[0044] In various embodiments, the hydrophobic thermoset or thermoplastic polymer may be physically entangled or chemically crosslinked with an ionic polymer (i.e., a polymer that includes a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups).

[0045] In some embodiments, the hydrophobic thermoset or thermoplastic polymer has ordered and disordered regions, and the ionic polymer may be located within the disordered regions.

[0046] In various embodiments, the hydrophobic thermoset or thermoplastic polymer may be selected from the group consisting of polymethyl methacrylate, polydimethyl siloxane, acrylonitrile butadiene styrene, polymethyl methacrylate, and polyurethanes (including polyether urethanes, polycarbonate urethanes, silicone polyether urethanes, and silicone polycarbonate urethanes).

[0047] In various embodiments, precursor polymers containing underivatized carboxylic acid groups and ionic polymers containing a combination of underivatized and sulfonic acid derivatized carboxylic acid groups can be formed from one or more monomers selected from acrylic acid, methacrylic acid, crotonic acid, linoleic acid, maleic acid, and fumaric acid.

[0048] In various embodiments, an article is provided that is formed from an ionic polymer that includes a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups (e.g., aminosulfonic acid derivatized carboxylic acid groups), where the concentration of underivatized carboxylic acid groups and the concentration of sulfonic acid derivatized carboxylic acid groups are substantially constant.

[0049] In various embodiments, an article is provided that is formed from an ionic polymer that includes a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups, where the concentration of underivatized carboxylic acid groups and / or the concentration of sulfonic acid derivatized carboxylic acid groups are relatively constant throughout the article. For example, an article may be provided in which (a) the concentration of underivatized carboxylic acid groups varies by at most + / - 10%, at most + / - 5%, at most + / - 2%, at most + / - 1%, or less throughout the article, and / or (b) the concentration of sulfonic acid derivatized carboxylic acid groups varies by at most + / - 10%, at most + / - 5%, at most + / - 2%, at most + / - 1%, or less throughout the article.

[0050] In various embodiments, articles are provided that are formed from ionic polymers that include a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups, where the concentration of underivatized carboxylic acid groups and / or the concentration of sulfonic acid derivatized carboxylic acid groups vary substantially throughout the article. For example, articles may be provided in which: (a) the concentration of underivatized carboxylic acid groups in the article varies between two points (i.e., two locations) in the article (e.g., between one side of the article and the opposite side of the article, between the outside of the article and the inside of the article, etc.) by at least + / -10%, at least + / -25%, at least + / -50%, at least + / -100%, at least + / -250%, at least + / -500%, at least + / -1000% or more; and / or (b) the concentration of sulfonic acid derivatized carboxylic acid groups in the article varies between two points (e.g., between one side of the article and the opposite side of the article, between the outside of the article and the inside of the article, etc.) by at least + / -10%, at least + / -25%, at least + / -50%, at least + / -100%, at least + / -250%, at least + / -500%, at least + / -1000% or more.

[0051] In various embodiments, articles are provided that are formed from ionic polymers that include a combination of underivatized carboxylic acid groups and sulfonate-derivatized carboxylic acid groups, where a gradient in the concentration of underivatized carboxylic acid groups and / or a gradient in the concentration of sulfonate-derivatized carboxylic acid groups is present, which in some of these embodiments may approximate the shape of a step function. For example, articles can be provided in which (a) the concentration of underivatized carboxylic acid groups decreases with increasing distance from at least one exterior surface of the article (e.g., decreases by at least 10%, at least 25%, at least 50%, at least 75%, at least 90% to up to 100% from at least one exterior surface of the article to an interior point (i.e., an internal location) in the article (also referred to herein as a point in the bulk of the article)); and (b) the concentration of underivatized carboxylic acid groups increases with increasing distance from at least one exterior surface of the article (e.g., increases by at least 10%, at least 20%, at least 50%, at least 100%, at least 200%, at least 500%, at least 1000% or more from at least one exterior surface of the article to an interior point in the article). (c) an article may be provided in which the concentration of sulfonate-derivatized carboxylic acid groups in the ionic polymer decreases with increasing distance from at least one exterior surface of the article (e.g., decreases by at least 10%, at least 25%, at least 50%, at least 75%, at least 90% up to 100% from at least one exterior surface of the article to an interior point in the article); or (d) an article may be provided in which the concentration of sulfonate-derivatized carboxylic acid groups in the ionic polymer increases with increasing distance from at least one exterior surface of the article (e.g., increases by at least 10%, at least 20%, at least 50%, at least 100%, at least 200%, at least 500%, at least 1000% or more from at least one exterior surface of the article to an interior point in the article).

[0052] The absolute molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups at various points in the article can vary widely. The molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups at any point in the article can range from 100,000:1 or more (including an infinite number if 100% of the underivatized carboxylic acid groups were converted to sulfonate-derivatized carboxylic acid groups) to 1:100 or less. For example, the molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups at any point in the article may be in the range of 100,000:1-50,000:1-25,000:1-10,000:1-5000:1-2500:1-1000:1-500:1-250:1-100:1-50:1-25:1-10:1-5:1-2.5:1-1:1-1:2.5-1:5-1:10-1:25-1:50-1:100 (i.e., a range between any two of the aforementioned ratios).

[0053] Articles formed from ionic polymers that include a combination of underivatized carboxylic acid groups and sulfonate-derivatized carboxylic acid groups can be provided in which the molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups is relatively constant throughout the article, or in which the molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups varies substantially within the article.

[0054] In embodiments providing articles formed from ionic polymers comprising a combination of underivatized and sulfonate-derivatized carboxylic acid groups, where the molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups in the article is relatively constant throughout the article, the molar ratio can vary throughout the article, for example, by up to + / - 10%, up to + / - 5%, up to + / - 2%, up to + / - 1% or less.

[0055] In embodiments that provide articles formed from ionic polymers that include a combination of underivatized and sulfonated carboxylic acid groups, where the molar ratio of sulfonated to underivatized carboxylic acid groups varies substantially throughout the article, there may be a variation in the molar ratio of sulfonated to underivatized carboxylic acid groups between two points in the article (e.g., between one side of the article and the opposite side of the article, between the outside of the article and the inside of the article, etc.) of at least + / -10%, at least + / -25%, at least + / -50%, at least + / -100%, at least + / -250%, at least + / -500%, at least + / -1000%, or more. In some embodiments, there may be a gradient in the molar ratio of sulfonated to underivatized carboxylic acid groups in the article. For example, the molar ratio of sulfonated to underivatized carboxylic acid groups may increase between one side of the article and the opposite side of the article, or may increase between the outside of the article and the inside of the article. As another example, the molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups can decrease between one side of the article and the opposite side of the article, or can decrease between the outer surface of the article and the inner surface of the article.

[0056] In this regard, as described above, an ionic polymer can be formed from an article comprising a precursor polymer comprising underivatized carboxylic acid groups by diffusing a coupling reagent into the article and diffusing a sulfonic acid-containing compound into the article, where the coupling reagent can be diffused into the solid article before, after, or at the same time as the sulfonic acid-containing compound is diffused into the article. As a result, the concentration gradients of underivatized carboxylic acid groups and sulfonic acid-derivatized carboxylic acid groups in the resulting article can be independently adjusted and therefore typically differ from each other. For example, in various embodiments, the molar ratio of the concentration of sulfonic acid-derivatized carboxylic acid groups to underivatized carboxylic acid groups can decrease with increasing distance from the outer surface of the article to the inner surface of the article.

[0057] A concentration gradient in sulfonate-derivatized carboxylic acid groups and / or underivatized carboxylic acid groups in the article can result in, for example, a stiffness and / or hydration gradient in the article.

[0058] Some embodiments include a second hydrophobic thermoset or thermoplastic polymer that may be disposed in a layer separate from the first hydrophobic thermoset or thermoplastic polymer or may be diffused throughout the first hydrophobic thermoset or thermoplastic polymer.

[0059] In some embodiments, a layer of another material is deposited on one side of the article formed from the ionic polymer containing a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups during the manufacturing process as a coating. This material may be added, for example, to the non-hydrated side of the article containing the gradient ionic polymer. The material may be a binder or a type of binder, and is physically, chemically, or physicochemically attached to the surface of the article formed from the ionic polymer, for example, the non-hydrated side of the article containing the gradient ionic polymer. Placing this material coating on this surface can increase the strength of the binder that is subsequently applied. In some embodiments, this strength is enhanced because the coating material and the binder are compositionally the same or similar. In other embodiments, the coating is the same material as that on the surface of the article. In some embodiments, the coating is at least partially a different material than that on the surface of the article. The coating may be a polymer, copolymer, or polymer blend, and in one embodiment is a copolymer of polymethylmethacrylate and urethane dimethacrylate. The coating may be a thin film applied during the manufacturing process of the implant and may be applied by a variety of means including, but not limited to, spin coating, spray coating, vapor deposition, solution casting, painting, and lithography. In other embodiments, one surface of the article is roughened by applying an organic solvent and / or by mechanical means (e.g., including, but not limited to, polishing, sandblasting, lithography, and / or lamination molding). In some embodiments, the coating is applied to the roughened surface. In other embodiments, the roughened surface is present without any additional coating.

[0060] Another aspect of the present disclosure provides a method for making a water-swellable IPN or semi-IPN from a hydrophobic thermoset or thermoplastic polymer comprising the steps of: placing a liquid (e.g., comprised of pure monomer(s) or monomer(s) in solution) containing one or more carboxylic acid group-containing monomers in contact with a hydrophobic thermoset or thermoplastic polymer in solid form, diffusing the one or more carboxylic acid group-containing monomers into the thermoset or thermoplastic polymer, and polymerizing the one or more carboxylic acid group-containing monomers to form an ionic polymer containing carboxylic acid groups in the thermoset or thermoplastic polymer, thereby forming a precursor IPN or semi-IPN having carboxylic acid groups.

[0061] A liquid containing one or more aminosulfonic acid compounds is then contacted with a precursor IPN or semi-IPN having carboxylic acid groups to diffuse the one or more aminosulfonic acid compounds into the precursor IPN or semi-IPN under conditions such that the one or more aminosulfonic acid compounds react with the carboxylic acid groups of the precursor IPN or semi-IPN to form amide bonds, producing a mixed anionic IPN or semi-IPN containing underivatized carboxylic acid groups and aminosulfonic acid derivatized carboxylic acid groups. For example, a mixture of the aminosulfonic acid compounds represented by the formula (H2N) above can be used. x R(SO3H) y The aminosulfonic acid reacts with the carboxylic acid group -COOH in the precursor IPN or semi-IPN to form -CONH(H2N) x-1 R(SO3H) y In various embodiments, a liquid containing a coupling reagent is contacted with the precursor IPN or semi-IPN prior to, simultaneously with, or after contact with a liquid containing one or more aminosulfonic acid compounds, such that the coupling reagent reacts with the carboxylic acid groups, thereby activating the carboxylic acid groups for forming amide bonds with one or more aminosulfonic acid compounds.

[0062] Some embodiments include swelling the mixed anionic IPN or semi-IPN with water, for example to form a hydration gradient from a first portion of the composition to a second portion of the composition. The method may also include swelling the mixed anionic IPN or semi-IPN with an electrolyte solution.

[0063] In some embodiments, the hydrophobic thermosetting or thermoplastic polymer is selected from polyurethanes, polymethylmethacrylates, polydimethylsiloxanes, acrylonitrile butadiene styrenes and polymethylmethacrylates, polyetherurethanes, polycarbonateurethanes, silicone polyetherurethanes, and silicone polycarbonateurethanes, among others. The carboxylic acid group-containing monomer solution used to form the ionic polymer containing carboxylic acid groups in the thermosetting or thermoplastic polymer may be selected from acrylic acid monomers, methacrylic acid monomers, crotonic acid monomers, linoleic acid monomers, maleic acid monomers, and fumaric acid monomers, among others, containing carboxylic acid groups.

[0064] Some embodiments include changing the precursor IPN or semi-IPN or mixed anionic IPN or semi-IPN from a first shape to a second shape by heating the precursor IPN or semi-IPN or mixed anionic IPN or semi-IPN.

[0065] Yet another aspect of the present disclosure provides a medical implant (such as an orthopedic implant) comprising a water-swellable mixed anionic IPN or semi-IPN comprising a hydrophobic thermosetting or thermoplastic polymer and an ionic polymer comprising a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups, the implant having a bone contacting surface shaped to conform to the bone surface. Some embodiments also include a fluid capsule disposed within an interior region of the implant. Some embodiments have an insert adapted to be inserted into the bone, and a joint interface portion adapted to be disposed in the joint space, such as a bone screw, suture, or staple adapted to engage the mixed anionic IPN or semi-IPN and bond the bone to the mixed anionic IPN or semi-IPN, and / or a stem extending from the bone contacting surface and adapted to be inserted into the bone. The medical implant may also incorporate a bearing element of another device, such as a metallic prosthesis.

[0066] The medical implant may also include a binder adapted to attach the medical implant to bone, for example, a bone ingrowth surface formed on the bone contact surface. In some embodiments, the ionic polymer comprising a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups forms a concentration gradient from a first portion of the implant to a second portion of the implant. Some embodiments have a second hydrophobic thermosetting or thermoplastic polymer adjacent to a first hydrophobic thermosetting or thermoplastic polymer, an ionic polymer comprising a combination of underivatized carboxylic acid groups and sulfonic acid derivatized carboxylic acid groups interpenetrating with at least the first hydrophobic thermosetting or thermoplastic polymer.

[0067] In some embodiments, implants formed from the ionic polymers described herein (including implants containing the water-swellable mixed anionic IPNs or semi-IPNs described herein) can have properties that mimic the stiffness and lubricity properties of natural cartilage. In some embodiments, implants formed from the ionic polymers described herein (including implants containing the water-swellable mixed anionic IPNs or semi-IPNs described herein) can be adapted and configured to replace cartilage in a joint. For example, the implant can have a shape selected from the group consisting of a cap, a cup, a plug, a mushroom, a cylinder, a stem, and a patch. The implants may be adapted to repair or replace cartilage in joints within the body, such as the knee (including the medial compartment of the knee, the patellofemoral joint, and the total knee), knee meniscus, condyles, patella, tibial plateau, ankle, elbow, shoulder (including the labrum), wrist (including the metacarpal, knuckle, thumb, and base of the thumb), glenoid cavity, hip (including the acetabular joint), intervertebral disc, spinal joint (including the facet joints), labrum, meniscus, ankle (including the metatarsal and toe joints), temporomandibular joint (including the temporomandibular joint), or wrist, as well as any parts thereof.

[0068] In some embodiments, the implants described herein can have at least a portion of the implant configured to temporarily deform during placement of the implant in the joint.

[0069] Yet another aspect of the present disclosure provides a method of orthopedic joint repair, comprising replacing natural cartilage with a water-swellable mixed anionic IPN or semi-IPN according to the present disclosure, including engaging the mixed anionic IPN or semi-IPN with a bone surface that defines the joint. The method may also include bonding, suturing, stapling, and / or screwing the mixed anionic IPN or semi-IPN to the bone surface. The method may also include incorporating the material as a bearing element of another device, such as a metallic prosthesis. The method may also include inserting a stem portion into the bone surface. The orthopedic joint may be selected from the group consisting of shoulder joints including the labrum, hip joints including the acetabular joint, wrist joints, finger joints, hand joints including the metacarpal joints, thumb joints, proximal thumb joints, ankle joints, elbow joints, ankle joints including the metatarsal joints and toe joints, temporomandibular joints including the temporomandibular joint, medial compartment joints of the knee, patellofemoral joints, total knee joints, femoral joints, acetabular joints, elbows, intervertebral discs, and spinal joints including the facet joints.

[0070] Yet another aspect of the present disclosure provides a marine hull coating comprising a water-swellable mixed anionic IPN or semi-IPN according to the present disclosure, the coating having a hull-contacting surface adapted to adhere to a marine hull. The coating may also include UV protection agents and / or antioxidants. [Brief description of the drawings]

[0071] [Figure 1] FIG. 1 is a schematic diagram of a method for forming an IPN or semi-IPN according to one embodiment of the present disclosure. From left to right: the thermoplastic material in this embodiment of the disclosure is a polyurethane that is converted into a semi-IPN of polyurethane and poly(acrylic acid). Carboxylic acid moieties are then derivatized to sulfonic acid moieties. [Diagram 2]1 is a schematic diagram of a sulfonation process according to one embodiment of the present disclosure, in which poly(acrylic acid) of a semi-IPN is reacted with taurine and (4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride) under basic conditions to derive poly(acrylic acid) and poly(sulfonic acid) derivatives of taurine. [Figure 3A-3F] Graphs illustrating the divalent percent weight loss of sulfonated (FIGS. 3A-E) and non-sulfonated (FIG. 3F) gradient poly(ether urethane)-poly(acrylic acid) (PEU-PAA) test articles across a range of PAA / PEU percentages as a function of total divalent ion concentration: (FIG. 3A) 17.6% PAA / PEU, (FIG. 3B) 22.2% PAA / PEU, (FIG. 3C) 25.5% PAA / PEU, (FIG. 3D) 27.6% PAA / PEU, (FIG. 3E) 40.7% PAA / PEU, (FIG. 3F) a non-sulfonated gradient PEU-PAA test article with 40.7% PAA / PEU. Lines were fitted to derive the percent weight loss per millimole of total divalent ion concentration for all test articles made with different PAA / PEU percentage amounts, with the slopes shown above each graph. Error bars represent standard error, n = 5 for each point. NS: p<0.1. [Figure 4] 1 is a graph of normalized sulfonate peak intensity of Raman microscopy spectra as a function of depth (mm) of sulfonated gradient PEU-PAA according to the present disclosure. Top: Represents an intensity map of the ratio of the -SO3 breathing mode (1045 cm-1) to one of the polyurethane breathing modes (1640 cm-1) through the depth (2 mm) of the sulfonated gradient PEU-PAA material. Bottom: Represents the cumulative distribution of the ratio of the -SO3 breathing mode (1045 cm-1) to one of the polyurethane breathing modes (1640 cm-1) over a thickness of 200 μm as a function of material depth. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0072] The present disclosure includes methods for modifying commonly available hydrophobic thermoset or thermoplastic polymers to impart qualities such as lubricity, permeability, electrical conductivity, and wear resistance. Such hydrophobic polymers do not typically absorb water and are generally useful for their mechanical strength, impermeability, and insulating capabilities. An exemplary list of hydrophobic polymers that can be modified by the methods of the present disclosure includes: acrylonitrile butadiene styrene (ABS), polymethyl methacrylate (PMMA), acrylic, celluloid, cellulose acetate, ethylene vinyl acetate (EVA), ethylene vinyl alcohol (EVAL), Kydex, a brand of acrylic / PVC alloy, liquid crystal polymer (LCP), polyacetal (POM or acetal), polyacrylate (acrylic), polyacrylonitrile (PAN or acrylonitrile), polyamide (PA or nylon), polyamide-imide (PAI), polyaryletherketone (PAEK or ketone), polyhydroxyalkanoate (PAEK ... Polyurethanes include, for example, polyphenylene ether ketones (PHAs), polyketones (PKs), polyesters, polyetheretherketones (PEEKs), polyetherimides (PEIs), polyethersulfones (PESs), polysulfones, chlorinated polyethylenes (PECs), polyimides (PIs), polymethylpentenes (PMPs), polyphenylene oxides (PPOs), polyphenylene sulfides (PPSs), polyphthalamides (PPAs), polystyrenes (PSs), polysulfones (PSUs), polyvinyl acetates (PVAs), polyvinyl chlorides (PVCs), polyvinylidene chlorides (PVDCs), Spectralon, styrene-acrylonitrile (SANs), polydimethylsiloxanes (PDMSs), and polyurethanes (PUs). As will be described herein, a wide variety of polyurethanes can be used with varying hard segment, soft segment, and chain extender compositions.

[0073] One aspect of the present disclosure exploits a feature of some modifiable thermosetting or thermoplastic hydrophobic polymers: the presence of ordered and disordered (amorphous) regions in the polymer. For example, some hydrophobic thermosetting or thermoplastic polymers, such as polyurethanes, are phase separated, which include a first region of hard segments and a second region of soft segments, the two regions exhibiting different solubilities for monomer interpenetration. In polyurethanes, the hard segments are primarily located in the ordered regions and the soft segments are primarily located in the disordered (amorphous) regions. (The starting polymer may, of course, include more than two regions without departing from the scope of the present disclosure.) This difference in properties between the two regions of the phase separated polymer allows the method of the present disclosure to impart new properties to the polymer, which may extend throughout the entire material or only through a portion of the material (e.g., in a specific region or gradient). For example, a non-lubricating polymer can be made lubricating, an otherwise non-conducting polymer can be made conductive, and an otherwise non-permeable polymer can be made permeable. Moreover, the process can be carried out repeatedly to introduce multiple new properties into the starting polymer.

[0074] In some embodiments, phase separation in a polymer allows for differential swelling of one or more separated phases in the polymer, for example, by solvents and / or monomers, which can be used to impart new properties. According to the present disclosure, for example, lubricity can be introduced into an otherwise non-lubricated material by adding and polymerizing one or more carboxylic acid group-containing monomers, followed by reaction with one or more sulfonic acid-containing compounds. In one embodiment, polymeric materials with high mechanical strength and lubricious surfaces can be produced from otherwise non-lubricated hydrophobic polymers. By converting otherwise hydrophobic materials into multiphase materials (materials with both solid and liquid (aqueous) phases), the present disclosure addresses the need in the art for materials with high lubricity and strength for use in medical, commercial, and industrial applications.

[0075] In some embodiments, the thermoplastic polyurethane-based polymer containing the network of hard and soft segments can be swollen with monomer and optional solvent together with initiator and crosslinker, thus swelling the soft segments with little effect on the hard segment material. This swelling process does not dissolve the polymer, but rather the hard segments act as physical crosslinks to hold the material together while the soft segments are absorbed into the monomer and optional solvent. After polymerization and crosslinking of the monomer and reaction with sulfonic acid-containing compound, a second network is formed in the presence of the first network, creating an IPN or semi-IPN in which the second polymer (i.e., the polymerized and sulfonated monomer) is primarily sequestered within the soft amorphous regions of the first polymer. Despite some degree of intramolecular transformation and further phase separation, the hard segments remain largely ordered and crystalline, providing structure and strength to the material.

[0076] The new properties provided by this IPN depend on the properties of the polymerized monomers introduced and the sulfonic acid-containing compounds introduced as a result. Examples of such new properties include lubricity, electrical conductivity, hardness, absorbency, permeability, photoreactivity and thermal reactivity. After optional swelling in a buffered aqueous solution, the second network of the mixed anionic IPN or semi-IPN is ionized and the mixed anionic IPN or semi-IPN is water swollen and lubricious. Therefore, hydrophilicity (i.e., water absorption) can be introduced into other hydrophobic materials. Hydrophobic polymeric materials, such as polyurethane or ABS, can penetrate various mixed anionic polymers (polymers containing a combination of underivatized carboxylic acid groups and aminosulfonic acid derivatized carboxylic acid groups) and absorb water.

[0077] In addition to absorption, various levels of permeability (water, ion, and / or solute movement) can be introduced into otherwise non-permeable materials. For example, hydrophobic polymeric materials such as polyurethane or ABS can penetrate the mixed anionic polymer and thus absorb water as described above. The hydration of the entire material allows for the movement of solutes and ions. The movement of solutes and ions as well as the permeability to water is made possible by the phase continuity of the hydrated phase of the mixed anionic IPN or semi-IPN. This can be useful in a variety of applications including drug delivery, separation methods, proton exchange membranes, and catalytic processes. Permeability can also be utilized to capture, filter, or chelate solutes as a liquid flowing on or through the material. Furthermore, because of this permeability, the material of the present disclosure can have increased resistance to creep and fatigue compared to its constituent hydrophobic polymers due to its ability to reabsorb fluids after sustained or repeated loading.

[0078] Additionally, any of the regions can be doped with a number of materials, such as antioxidants, ions, ionomers, contrast agents, particles, metals, pigments, dyes, biomolecules, polymers, proteins, and / or therapeutic agents, any of which can be physically or chemically incorporated (e.g., covalently bonded to or otherwise included as one or more components of the IPN or semi-IPN).

[0079] For example, if acryloxy, methacryloxy, acrylamide, allyl ether, or vinyl functional groups are incorporated into one or both ends of the thermosetting or thermoplastic polymer and then cured by UV or temperature in the presence of an initiator, the hydrophobic thermosetting or thermoplastic polymer can be further crosslinked or copolymerized with a carboxylic acid group-containing polymer. As an example, polyurethane dimethacrylate or polyurethane bisacrylamide can be used in the first network by curing in the presence of a solvent (e.g., dimethylacetamide) and then evaporating the solvent. Adding chemical crosslinks (not just physical crosslinks) to the IPN increases the level of mechanical stability against creep or fatigue caused by continuous dynamic loading.

[0080] In addition, when the thermoplastic polymer is a polyurethane, crosslinks can be created in the polyurethane using multiarm (multifunctional) polyols or isocyanates. In this case, a fully interpenetrating polymer network (rather than a semi-interpenetrating polymer network) is created. The result is a composite material with the high strength and toughness of polyurethane and the lubricious surface and multiphase bulk behavior of ionic polymers. Alternatively, other crosslinking methods can be used, including but not limited to gamma or electron beam irradiation. These characteristics are useful for bearing applications, such as artificial joint surfaces, or as more biocompatible, antithrombogenic long-term implants in other areas of the body, such as the vasculature or skin. When swollen with water, they also allow for the absorption of solutes, such as therapeutic agents or drugs, for localized delivery to target areas of the body.

[0081] In another embodiment of the present disclosure, a hydrophobic thermosetting or thermoplastic polymer can be attached to a carboxylic acid group-containing polymer. For example, polyurethane can be attached via a vinyl end group. Depending on the reactivity ratio between the polymerizing end group and the monomer, different chain configurations can be produced. For example, if the reactivity of the monomer with itself is much greater than the reactivity of the end group with the monomer, the carboxylic acid group-containing polymer is almost completely formed before being added to the chain. On the other hand, if the reactivity of the monomer and the end group are similar, a random graft type copolymerization occurs. The monomers and end groups can be selected based on their reactivity ratios, for example, by using a table of relative reactivity ratios published in The Polymer Handbook. The result is a hybrid copolymer / interpenetrating polymer network.

[0082] Any number of ethylenically unsaturated monomers or macromonomers (i.e., having reactive double bonds / vinyl groups) or combinations thereof can be used alone or in combination with various solvents and can be selectively introduced into one or more phases of the polymer, so long as at least a portion of such monomers contain carboxylic acid functionality. Other monomers include, but are not limited to, dimethylacrylamide, acrylamide, N-isopropylacrylamide (NIPAAm), methyl acrylate, methyl methacrylate, hydroxyethyl acrylate / methacrylate.

[0083] In one embodiment, a preformed thermoplastic polymer may be immersed in acrylic acid (or acrylic acid (1%-100%) solution or other vinyl monomer solution) along with a crosslinker (e.g., triethylene glycol dimethacrylate or N,N'-methylenebisacrylamide) and a photoinitiator (e.g., 2-hydroxy-2-methylpropiophenone). The acrylic acid solution may be based on water, a salt buffer, or an organic solvent such as dimethylacetamide, acetone, ethanol, methanol, isopropyl alcohol, toluene, dichloromethane, propanol, dimethylsulfoxide, dimethylformamide, or tetrahydrofuran. The polymer may be swollen by the monomer (e.g., due to solvation of soft segments in the polymer). The monomer content in the swollen polymer may range from as little as about 1% up to about 90%.

[0084] It is noted that while various aspects of the present disclosure are illustrated herein using acrylic acid as an exemplary monomer, it should be understood that various carboxylic acid group-containing monomers are also contemplated, such as one or more of the following, among others: acrylic acid, methacrylic acid, crotonic acid, linoleic acid, maleic acid, and fumaric acid. Similarly, it is noted that while various aspects of the present disclosure are illustrated herein generally using poly(acrylic acid) as an exemplary polymer, it should be understood that polymers of various carboxylic acid group-containing monomers may also be applicable, such as one or more of the following, among others: acrylic acid, methacrylic acid, crotonic acid, linoleic acid, maleic acid, and fumaric acid.

[0085] The monomer-swollen polymer may then be removed and placed into a glass, quartz, or transparent polymer mold and then exposed to UV light (or elevated temperature) to initiate polymerization and crosslinking of the monomer. Alternatively, instead of using a mold, the monomer-swollen polymer may be polymerized while fully or partially exposed to air or an inert atmosphere (e.g., nitrogen or argon), or in the presence of another liquid, such as oil (e.g., paraffin, mineral oil, or silicone oil). Depending on the initiator used, exposure to UV, IR, or visible light, chemicals, electrical charges, or elevated temperature results in polymerization and crosslinking of the carboxylic acid group-containing monomers in the hydrophobic polymer. As an example, a monomer (e.g., acrylic acid) is polymerized to form an ionic polymer containing carboxylic acid groups in a preformed thermoplastic hydrophobic matrix, forming an interpenetrating polymer network ("IPN"). The solvent can be extracted by heating and convection or by solvent extraction. Solvent extraction requires the extraction of the solvent from the polymer using a different solvent (e.g., water), while heating or convection relies on the evaporation of the solvent.

[0086] Sulfonation of the IPN may then be carried out via an amidation reaction of the carboxylic acid groups with an aminosulfonic acid compound, such as taurine, using 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride as a catalyst.

[0087] Swelling of the mixed anionic IPN or semi-IPN in an aqueous solution at neutral pH, such as phosphate buffered saline (or other saline, such as divalent cation solutions described elsewhere herein), results in ionization of carboxylic acid and sulfonic acid groups and further swelling with water and salt. The resulting swollen mixed anionic IPN or semi-IPN has a lubricious surface provided by the hydrophilic charged polymer and high toughness and mechanical strength provided by the thermoplastic polymer. In the case of polyurethane-based mixed anionic IPN or semi-IPN, the mixed anionic IPN or semi-IPN has a structure in which the crystalline hard segments in the polyurethane act as physical crosslinks in the first network, while chemical crosslinks exist in the second network.

[0088] After synthesis, the material can also be crosslinked using gamma radiation or electron beam irradiation. In one example, polyurethane / polyacrylic acid can be synthesized and then crosslinked by gamma radiation at a dose of, for example, 5, 10, 15, 20, or 25 kGy. In this case, the polymerization of polyacrylic acid can be carried out in the absence of a crosslinking agent, and the material can be exposed to gamma radiation after the formation of the polymer blend (physical IPN). It is known in the art that crosslinking of poly(acrylic acid) hydrogels using gamma radiation shows a dose-dependent effect on the crosslinking of the polymer. In the case of polyurethane, the polyurethane polymer can be a commercially available material, a modified version of a commercially available material, or a new material.

[0089] A number of chemistries and stoichiometries can be used to make polyurethane polymers. In the hard segments, the isocyanates used are 1,5 naphthalene diisocyanate (NDI), isophorone isocyanate (IPDI), 3,3-toluene diisocyanate (TODI), methylene bis(p-cyclohexyl isocyanate) (H 12MDI), cyclohexyl diisocyanate (CHDI), 2,6 tolylene diisocyanate or 2,4 toluene diisocyanate (TDI), hexamethyl diisocyanate, or methylene bis(p-phenylisocyanate). In the soft segment, the chemicals used include, for example, polyalkylene oxides, such as polyethylene oxide (PEO), polypropylene oxide (PPO), polybutylene oxide (PBO), polybutadiene, polydimethylsiloxane (PDMS), polyethylene adipate, polycaprolactone, polytetramethylene adipate, polyisobutylene, polyhexamethylene carbonate glycol, poly(1,6 hexyl 1,2-ethyl carbonate). When using end groups that react with isocyanates, any number of telechelic polymers may be used in the soft segment. As examples, poly(vinylpyrrolidone) with hydroxyl or amine end groups, dimethylacrylamide, carboxylate or sulfonated polymers, telechelic hydrocarbon chains (with hydroxyl and / or amine end groups), dimethylolpropionic acid (DMPA), or combinations of these with each other or with other soft segments as mentioned above (e.g., PDMS) can be used.

[0090] Chain extenders include, for example, 1,4-butanediol, ethylenediamine, 4,4'-methylenebis(2-chloroaniline) (MOCA), ethylene glycol, and hexanediol. Other compatible chain extenders can be used alone or in combination. Crosslinking chain extenders containing isocyanate-reactive end groups (e.g., hydroxyl or amine) and vinyl-based functional groups (e.g., vinyl, methacrylate, acrylate, allyl ether, or acrylamide) may be used in place of some or all of the chain extenders. Examples include 1,4-dihydroxybutene and glycerol methacrylate. Alternatively, crosslinking can be achieved using a polyol containing three or more hydroxyl groups to react with isocyanates, such as glycerol.

[0091] In some embodiments, at least 1% of the monomers in the second network contain a carboxylic acid group. In one such embodiment, poly(acrylic acid) (PAA) hydrogel is used as the second polymer network formed from an aqueous solution of acrylic acid monomer. Other carboxylic acid group-containing monomers include, for example, methacrylic acid. These other monomers may range from 1% to 99% in either water or organic solvent, or may be in pure (100%) form. One embodiment of the monomers used to form the second network can be described by the following characteristics: (1) they can swell without dissolving the polyurethane, (2) they are polymerizable, and (3) they contain a carboxylic acid group.

[0092] Other embodiments use additional comonomers that may be non-ionic, such as acrylamide, methacrylamide, N-hydroxyethylacrylamide, N-isopropylacrylamide, methyl methacrylate, N,N-dimethylacrylamide, N-vinylpyrrolidone, 2-hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, or derivatives thereof.

[0093] Any type of compatible crosslinking agent may be used to crosslink the second network in the presence of any of the above first networks, such as ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate (or diacrylate), triethylene glycol dimethacrylate (or diacrylate), tetraethylene glycol dimethacrylate (or diacrylate), polyethylene glycol dimethacrylate or polyethylene glycol diacrylate, methylene bisacrylamide, N,N'-(1,2-dihydroxyethylene) bisacrylamide, derivatives, or combinations thereof. A number of photoinitiators may also be used, depending on their solubility in the precursor solution / material. These include, but are not limited to, 2-hydroxy-2-methylpropiophenone and 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone. In addition, other initiators may be used, such as benzoyl peroxide, 2-oxoglutaric acid, azobisisobutyronitrile, or potassium persulfate (or sodium persulfate). As an example, benzoyl peroxide is useful for temperature initiated polymerization, while azobisisobutyronitrile and sodium persulfate are useful as radical initiators.

[0094] In another embodiment, a solvent can be used as a vehicle to deliver monomers that would not mix (or solubilize) the polymer into a single-phase (or multi-phase) polymer. The solvent must be carefully selected based on the specific qualities and phases of the polymer and monomer. As an example, acetic acid can swell but does not dissolve many polyurethanes. Thus, acetic acid can be used to carry other monomers that would not go into polyurethane, such as acrylamide solutions, inside the entire polyurethane. This selectively polymerizes the acrylamide within the single phase of the polyurethane. The acetic acid can then be washed off to leave a polyurethane with one or more new properties. Other solvents that can be used include, but are not limited to, methanol, propanol, butanol (or any alkyl alcohol), acetone, dimethylacetamide, tetrahydrofuran, diethyl ether, or combinations thereof. Solvents with varying degrees of swelling may be selected taking into account the solubility in the phases of the polymer. The solubility of the solvent and the components of the material to be swollen can be obtained from a polymer textbook, such as The Polymer Handbook, or can be experimentally measured.

[0095] After polymerization of the carboxylic acid group-containing monomers, any optional comonomers, and any crosslinking agents, the resulting composition is then reacted with one or more sulfonic acid-containing compounds to sulfonate some of the carboxylic acid group-containing monomers and complete the second network. In a particular embodiment, sulfonation of the precursor IPN or semi-IPN with carboxylic acid groups is achieved through an amidation reaction with taurine using 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride as a catalyst. The chemical reaction process for making the mixed anionic IPN or semi-IPN is shown in Figure 1. The sulfonation chemistry used to convert the carboxylic acid groups to sulfonate groups is shown in Figure 2. Of course, the process is not limited to PAA, but is applicable to virtually any polymer containing carboxylic acid groups.

[0096] Among the applications of the present disclosure are the creation of hydrophilic lubricious sizing or coatings to reduce biofilm formation and / or barnacle formation in ships, other vessels or waterborne objects, or in conduits. Additionally, the present disclosure can be used as a method for manufacturing, for example, engines, pistons, or other machines or machine parts for bearing and moving parts applications. The present disclosure can also be used in artificial joint systems or long-term implants in other areas of the body, such as stents and catheters for the vascular or urinary systems, or skin implants, patches, or dressings.

[0097] The present disclosure can be used to create a composition gradient in a homogeneous starting polymeric material. A gradient can be formed along the thickness direction of the material, with the mixed anionic IPN or semi-IPN formed on one side and the concentration decreasing to the opposite side (e.g., substantially only the starting polymeric material). The mixed anionic IPN or semi-IPN concentration gradient can be radial in the material, with the mixed anionic IPN or semi-IPN having the highest concentration on the outer surface and the mixed anionic IPN or semi-IPN having the lowest concentration in the center or core. In one method of making a thermoplastic gradient mixed anionic IPN or semi-IPN according to the present disclosure, a monomer solution is imbibed on one side of the thermoplastic material with a photoinitiator and a crosslinker, and then the monomer is polymerized and crosslinked (e.g., by UV light) in the thermoplastic material to form a gradient mixed anionic IPN or semi-IPN. In one embodiment, the mixed anionic IPN or semi-IPN made in the gradient hydrophobic polymer is swollen in a carboxylic acid-containing monomer, which is only on one side or the swelling time is limited, resulting in incomplete diffusion of the monomer through the entire hydrophobic polymer. This is particularly useful in the creation of osteochondral grafts of orthopedic joint replacement materials. For example, in the case of cartilage replacement materials, one side of the material is smooth and water-swellable, while the other side remains solid (pure thermoplastic). Alternatively, if the diffusion of carboxylic acid-containing monomers into the hydrophobic polymer is precisely controlled by the timing of the monomers' penetration into the bulk, a bulk material can be created with an outer surface of a mixed anionic IPN or semi-IPN and a "core" of only hydrophobic polymer. The swelling differential resulting from this configuration can result in residual stresses (compressibility on the swollen side, tension on the non-swollen side) that can help enhance the mechanical and fatigue behavior of the material. In the case of materials with a thickness gradient, a base of hydrophobic polymer-only material can be used to fix, adhere, or suture the device to an anatomical area or subject. This base can be limited to a small area or can be large (e.g., skirt) and can extend outward as a single or composite component (e.g., strap). Internal stresses created in the thermoplastic during the process or after swelling can be reduced by temperature-induced annealing.For example, the polymer may be annealed using temperatures between 60 and 120°C for various times (30 minutes to several hours), heat can be applied by hot surface in an oven, irradiation, or a heat gun. Thermoplastics can be later crosslinked using, for example, gamma or electron beam irradiation.

[0098] The articles made from the mixed anionic IPN and semi-IPN of the present disclosure may also be formed in a laminate structure. In one embodiment, the mixed anionic IPN or semi-IPN structure is composed of a hydrophilic polymer, such as sulfonated poly(acrylic acid) (sPAA), which interpenetrates a first thermoplastic polymer, such as polyether urethane, and is formed on top of a second thermoplastic polymer, such as polycarbonate urethane. The first and second thermoplastic polymers themselves may be composed of multiple layers with different hardness and properties. In addition, many more than two thermoplastic layers may be used, and one or more thermoplastic polymers may be crosslinked. Finally, non-thermoplastic components may be incorporated into this structure.

[0099] Heat can be used to reanneal the physical crosslinks of the polymer (e.g., hard segments in polyurethane) on the hydrophobic polymer side of the gradient mixed anionic IPN or semi-IPN, resulting in a different desired curvature (including both convex and concave curvatures on the hydrophobic polymer side of the gradient mixed anionic IPN or semi-IPN) after bending (e.g., on a mold or die) and cooling. Of course, other shapes can be formed as desired. The use of a thermoplastic polymer as the hydrophobic polymer facilitates the molding of the device into the desired shape, for example, by injection molding, reactive injection molding, compression molding, or dip casting. The molded device can then be subjected to a subsequent network infiltration and polymerization step to generate a new mixed anionic IPN or semi-IPN material.

[0100] Molding of mixed anionic IPN and semi-IPN articles according to the present disclosure can be performed in situ, e.g., within the human body, for example, by heating a thermoplastic mixed anionic IPN or semi-IPN to allow it to wrap around the curve of the femoral head or to conform to the curve of the acetabulum.

[0101] The shaped or unshaped mixed anionic IPN and semi-IPN articles made according to the present disclosure may also be attached to other surfaces. For example, a bonding agent, such as a solvent, cement, or glue, can be used to attach the thermoplastic gradient mixed anionic IPN or semi-IPN article to the surface of the joint interface. The addition of a solvent, for example, locally dissolves the material, and after the solvent dries on contact with the surface, the thermoplastic polymer adheres to the surface. This approach can be used to bond the gradient mixed anionic IPN or semi-IPN to bone surfaces in joints. The bonding agent can be sterilized in a disposable syringe in some embodiments.

[0102] In certain embodiments, the binder may include urethane dimethacrylate and methyl methacrylate (MMA). The binder may be cured using radiation, such as visible, infrared, or ultraviolet light, with a photoinitiator, a thermal initiator, a chemical initiator or catalyst, and / or a redox-activated initiation system, such as those including camphorquinone and N,N-dimethyl-p-toluidine. A combination of photoinitiating and non-photoinitiating systems (e.g., heat, chemicals, and / or redox systems) may also be used. Accelerators may also be used. The urethane dimethacrylate may include a soft segment selected from, for example, polyalkylene oxides such as polyethylene oxide (PEO), polypropylene oxide (PPO), and polybutylene oxide (PBO), polybutadiene, polydimethylsiloxane (PDMS), polyethylene adipate, polycaprolactone, polytetramethylene adipate, polyisobutylene, polyhexamethylene carbonate glycol, and poly(1,6 hexyl 1,2-ethyl carbonate). The urethane dimethacrylate may include, for example, 1,5 naphthalene diisocyanate (NDI), isophorone isocyanate (IPDI), 3,3-bitoluene diisocyanate (TODI), methylene bis(p-cyclohexyl isocyanate) (H 12 The urethane dimethacrylate component may comprise, for example, about 70 to 90 weight percent of the binder.

[0103] Generally, in one embodiment, a system is provided that includes an article that includes a mixed anionic IPN or semi-IPN of the present disclosure and an adhesive kit that includes a bonding agent (eg, a solvent, cement, glue, or the like).

[0104] Generally, in one embodiment, a packaged article is provided that includes an article that includes a mixed anionic IPN or semi-IPN according to the present disclosure. In some embodiments, a divalent cation-containing solution that includes one or more divalent metal cations is included within the sterile package.

[0105] This and other embodiments can include one or more of the following features: An adhesive kit can include a first mixture including at least one of a urethane dimethacrylate oligomer and a methyl methacrylate monomer, a first reservoir including at least one of a photoinitiator and a thermal initiator, and an inhibitor, a second mixture including at least one of a urethane dimethacrylate monomer and a methyl methacrylate monomer, and a second reservoir including an accelerator, and instructions for use, where at least one of the first and second reservoirs can include the urethane dimethacrylate monomer, and at least one of the first and second reservoirs can include the methyl methacrylate monomer.

[0106] Both the first and second reservoirs can include urethane dimethacrylate monomers and methyl methacrylate monomers. The second reservoir can further include an inhibitor. The system can further include poly(methyl methacrylate). The system can further include a third reservoir including poly(methyl methacrylate) powder. The first mixture, the second mixture, and poly(methyl methacrylate) can define component weights, and the weight of the poly(methyl methacrylate) powder can comprise about 1% to about 70% of the component weights. The system can further include polystyrene. The system can further include a photoinitiator and a thermal initiator. The first reservoir can include a first chamber in a syringe, and the second reservoir can include a second chamber in a syringe, and the syringe can be configured to combine the first mixture with the second mixture to create the adhesive mixture. The system can further include a nozzle connected to the syringe configured to dispense the adhesive mixture. The first reservoir and the second reservoir can each contain about 0% (w / w) to about 100% (w / w), typically about 1% (w / w) to about 99% (w / w) of urethane dimethacrylate oligomer and / or 0% (w / w) to about 100% (w / w), typically about 1% (w / w) to about 99% (w / w) of methyl methacrylate. The first reservoir and / or the second reservoir can each contain about 0% (w / w) to about 100% (w / w), typically about 1% (w / w) to about 99% (w / w) of methyl methacrylate. The at least one initiator can contain between 0% (w / w) to about 5% (w / w), typically about 1% (w / w) to about 5% (w / w) of a photoinitiator including camphorquinone. The at least one initiator may comprise a thermal initiator including benzoyl peroxide at between 0% (w / w) and about 5% (w / w), typically about 1% (w / w) and about 5% (w / w). The accelerator may comprise N,N-dimethyl-p-toluidine at between 0% (w / w) and about 5% (w / w), typically about 1% (w / w) and about 5% (w / w). The inhibitor may comprise hydroquinone at between 0% (w / w) and about 5% (w / w), typically about 1% (w / w) and about 5% (w / w).The system may further include an additive configured to prevent infection. The system may further include an antibiotic. The system may further include a radiopaque material. The first mixture may define a viscosity of between about 1 Pa.s and 5000 Pa.s.

[0107] In one embodiment, the adhesive kit comprises from about 0% (w / w) to about 100% (w / w), typically from about 1% (w / w) to about 99% (w / w) of a urethane dimethacrylate oligomer and / or from about 0% (w / w) to about 100% (w / w), typically from about 1% (w / w) to about 99% (w / w) of a methyl methacrylate; from about 0% (w / w) to about 100% (w / w), typically from about 1% (w / w) to about 99% (w / w) of a methyl methacrylate; The system may be comprised of a single reservoir containing methyl methacrylate, an optional initiator (e.g., which may include at least one of a photoinitiator and a thermal initiator) in an amount of typically about 0% (w / w) to about 5% (w / w), such as about 1% (w / w) to about 5% (w / w), and an optional accelerator in an amount of typically about 0% (w / w) to about 5% (w / w), such as about 1% (w / w) to about 5% (w / w). The single reservoir may include a chamber in a syringe. The system may further include a nozzle connected to the syringe configured to dispense the curable adhesive. The initiator may include a photoinitiator, including camphorquinone, in an amount of between 0% (w / w) to about 5% (w / w), such as about 1% (w / w) to about 5% (w / w). The accelerating agent may comprise between 0% (w / w) and about 5% (w / w), typically about 1% (w / w) and about 5% (w / w) of N,N-dimethyl-p-toluidine. The inhibitor may comprise between 0% (w / w) and about 5% (w / w), typically about 1% (w / w) and about 5% (w / w) of hydroquinone. The system may further comprise an additive configured to prevent infection. The system may further comprise an antibiotic. The system may further comprise a radiopaque material. The first mixture may define a viscosity between about 1 Pa.s and 5000 Pa.s.

[0108] For example, the mixed anionic IPN and semi-IPN compositions of the present disclosure formed by the method of the present disclosure may be used in a variety of situations. One particular use is as artificial cartilage in osteochondral grafts. The present disclosure provides bone-sparing arthroplasty devices based on interpenetrating polymeric networks that mimic the molecular structure, as well as the elastic modulus, fracture strength, and lubricious surface of natural cartilage. Emulating at least some of these structural and functional aspects of natural cartilage, the mixed anionic semi-IPN and anionic IPN of the present disclosure form the basis of a novel bone-sparing "biomimetic joint surface reconstruction" joint replacement. Such devices, designed to replace only cartilage, are assembled into a complete flexible implantable device featuring a smooth articular surface and an osteointegrable bone interface.

[0109] In principle, devices can be made for all articular surfaces in the body. For example, a device covering the tibial plateau requires a similar bone preparation and polymer sizing process. For a device covering the femoral head of a hip joint, a cap-shaped device fits snugly to the contours of the femoral head. For a device lining the acetabulum, a hemispherical cup-shaped device can be stretched over the rim and snapped into place in the socket, providing a mating surface with the femoral head. In this manner, both hip joints of a patient can be repaired, creating a cap-on-cap joint. However, if only one side is damaged, only one side can be capped, creating a joint with the cap attached over the cartilage. In addition, the material of the present disclosure can be used to cap or line the joint surface of another joint replacement or articular surface reconstruction device (typically made of metal) to act as an alternative bearing surface.

[0110] Using the present disclosure, a process similar to that of the hip joint is used to create a cap-shaped device for the shoulder joint (also a ball and socket joint). For example, a shallow cup can be created to line the inner surface of the glenoid cavity. Additionally, devices for other joints of the hand, fingers, elbow, ankle, foot, and intervertebral surfaces can also be created using this "capping" concept. In one embodiment in the distal femur, the distal femur device volume follows the contour of the bone while preserving the anterior and posterior cruciate ligaments.

[0111] The mixed anionic IPNs and semi-IPNs of the present disclosure can be used as cartilage replacement plugs in joints of the body where cartilage has been damaged, as described below.

[0112] For example, the mixed anionic IPNs and semi-IPNs of the present disclosure made according to the methods of the present disclosure can be used as fully or partially synthetic osteochondral grafts. The osteochondral grafts consist of a smooth, cartilage-like synthetic bearing layer, which can be fixed to porous bone or synthetic porous bone-like structures. The bearing layer has two regions: a lubricious surface layer and a rigid bone anchoring layer. In one embodiment, the upper smooth region of the bearing layer consists of an interpenetrating polymer network composed of two polymers. The first polymer can be a hydrophobic thermoplastic polymer with high mechanical strength, including but not limited to polyether urethane, polycarbonate urethane, silicone polyether urethane, and silicone polycarbonate urethane, or materials incorporating urea linkages thereof, or materials incorporating urea linkages thereof (e.g., polyurethane urea). The second polymer can be a hydrophilic polymer derived from a carboxylic acid group-containing monomer, including but not limited to acrylic acid, which subsequently undergoes a sulfonation process, in which the carboxylic acid group-containing monomer is reacted with a sulfonic acid-containing compound. The lower region of the bearing layer (bone anchoring layer) may be a rigid non-resorbable thermoplastic polymer that can be made to flow by ultrasonic welding vibrations, ultrasonic energy, laser energy, heat, RF energy and electrical energy. The bone anchoring layer is used to fix the bearing layer to the bone or bone-like porous structure. If porous bone is used, it may be human or animal cancellous bone. If a synthetic bone-like material is used, it may be made of porous calcium phosphate (and / or other materials including but not limited to porous carbonate apatite, beta-tricalcium phosphate, or hydroxyapatite), or a porous resorbable or non-resorbable thermoplastic polymer as described above (including but not limited to polycarbonate urethane, polyether urethane, PLA, PLLA, PLAGA, and / or PEEK). The bearing layer is fixed to the porous bone or bone-like structure by the application of pressure in combination with energy that melts the bone anchoring material and causes it to flow into the pores or voids of the bone or bone-like structure after the energy source is removed and the material resolidifies.Energy sources can include, but are not limited to, vibration, ultrasonic energy, laser energy, heat, RF energy, and electrical energy.

[0113] In various embodiments, the compositions of the present disclosure can be used to form devices for partial or complete reconstruction of damaged joints within a mammal (animal or human). These devices can be secured to the bone by a number of means, such as press fits, screws (resorbable or non-resorbable metal or plastic), sutures (resorbable or non-resorbable), glues, adhesives, light-curable adhesives (e.g., polyurethane or resin-based), or bonding agents (e.g., polymethylmethacrylate or calcium phosphate, or dental cement).

[0114] Osteochondral graft implants formed from the mixed anionic IPNs or semi-IPNs of the present disclosure can be used to replace or reinforce cartilage in joints, such as the hip or shoulder joint. The implants can slip off the head of the humerus or femur. In some embodiments, the implants can include openings to accommodate ligaments or other anatomical structures.

[0115] Implants and other articles can be made in a variety of complex shapes according to the present disclosure. For example, an osteochondral graft can be formed from the mixed anionic IPNs or semi-IPNs of the present disclosure that can be used alone or in any combination needed to replace or reinforce cartilage in the knee joint. For example, an osteochondral graft can be adapted to engage the femoral condyle (or only one condyle), can be adapted to engage one or both sides of the tibial plateau, can be adapted to engage the patella to articulate with an osteochondral graft adapted to engage the patellofemoral groove, and / or can be adapted to engage the lateral and medial meniscus.

[0116] Osteochondral grafts may also be used in other joints (e.g., finger, hand, ankle, elbow, foot, or spine). Labrum prostheses may be formed from the mixed anionic IPN or semi-IPN of the present disclosure for use in replacing or reconstructing the labrum of the shoulder or hip. The mixed anionic IPN or semi-IPN of the present disclosure may be used as a bursa osteochondral graft, a labrum osteochondral graft, a glenoid osteochondral graft, and a humeral head osteochondral graft. In some embodiments, the mixed anionic IPN or semi-IPN of the present disclosure may be used as a prosthesis to resurface an intervertebral surface.

[0117] The mixed anionic IPN and semi-IPN compositions of the present disclosure can be formed as an artificial cartilage plug for partial reconstruction of articular surfaces. For example, an artificial cartilage plug can be formed from the gradient mixed anionic IPN composition of the present disclosure. The plug can have a stem portion formed on the thermoplastic polymer side of the article and can be adapted to be inserted into a hole or opening in a bone. The head of the plug is formed to be a lubricious mixed anionic IPN or semi-IPN as described above. The stem can be pushed into the hole or opening in the bone, leaving the lubricious mixed anionic IPN surface exposed to function as an artificial cartilage.

[0118] Artificial cartilage plugs formed from the mixed anionic IPNs or semi-IPNs of the present disclosure are provided with stems having helical projections that form threads for anchoring the plug to bone.

[0119] The embodiments of the compositions of the present disclosure can be used to create a two-sided lubricious implant. The implant can be sized and configured to replace a spinal disc. The implant can have a lubricious mixed anionic IPN or semi-IPN surface (e.g., formed as described above) on the upper and lower sides. A knee spacer can be formed with a wedge-shaped cross section. Similar to the disc prosthesis, the spacer also has a lubricious mixed anionic IPN or semi-IPN surface on the upper and lower sides.

[0120] Other variations and modifications to the above compositions, articles and methods are described below.

[0121] The hydrophobic polymers can be commercially available or custom made and can be made by many methods, such as extrusion, injection molding, compression molding, reaction injection molding (RIM) or solvent casting. The first polymer can be uncrosslinked or crosslinked by various means. Either polymer can be crosslinked, for example, by gamma or electron beam irradiation.

[0122] Any number of ethylenically unsaturated monomers or macromonomers (e.g., containing reactive double bonds) or combinations thereof can be used as the basis for the second or subsequent network, so long as a carboxylic acid group-containing monomer is included. These include, but are not limited to, those containing vinyl, acrylate, methacrylate, allyl ether, or acrylamide groups. Any number of pendant functional groups can be conjugated to these ethylenically unsaturated groups, including, but not limited to, carboxylic acids, esters, alcohols, ethers, phenols, aromatic groups, or carbon chains.

[0123] The hydrophobic polymer may be a polyurethane-based polymer, such as: polyether urethane, polycarbonate urethane, polyurethane urea, silicone polyether urethane, or silicone polycarbonate urethane. Other polyurethanes with other hard segments, soft segments, and chain extenders are also possible.

[0124] Other polymers can be used as hydrophobic polymers, for example homopolymers or copolymers of silicone (polydimethylsiloxane) or polyethylene.

[0125] When a polyurethane-based polymer is used as the hydrophobic polymer, the degree of physical and chemical crosslinking of the polyurethane-based polymer can vary from only physical crosslinking (thermoplastic) to extensive chemical crosslinking. In the case of chemical crosslinking, the crosslinkable polyurethane can be used alone or in a mixture with a thermoplastic (non-crosslinked) polyurethane.

[0126] The polymerization conditions (ie, atmospheric oxygen, UV light intensity, UV light wavelength, exposure time, temperature) and sulfonation conditions can be varied.

[0127] The orientation and gradient of the composition gradient can be varied by various means, such as the time and / or method of immersion in the monomer and / or aminosulfonic acid compound, and the application of external hydrostatic positive or negative pressure.

[0128] Hydrophobic polymers can be made porous by various techniques, such as foaming or salt leaching. After swelling a porous polymer (such as PU) with a monomer (such as AA) and subsequent polymerization of AA and reaction with aminosulfonic acid, a porous mixed anionic IPN is formed.

[0129] Additional thermoplastic layers can be added to either the IPN side of the material or just the thermoplastic polymer side by curing or drying a new thermoplastic polymer against the surface. The layers can be all the same material or different materials (e.g., ABS+polyurethane, polyetherurethane+polycarbonateurethane, etc.).

[0130] A number of different solvents may be used during the synthesis of the polyurethane, the secondary network, or both, including but not limited to dimethylacetamide, tetrahydrofuran, dimethylformamide, ethanol, methanol, acetone, water, dichloromethane, propanol, methanol, or combinations thereof.

[0131] A number of coupling reagents may be used to promote the reaction of the aminosulfonic acid compound with the carboxylic acid group-containing polymer, including triazine-based coupling reagents, carbodiimides, phosphonium and aminium salts, and fluoroformamidinium coupling reagents. In certain embodiments, the coupling reagent may be 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM).

[0132] The extent and depth of derivatization (i.e., sulfonation) of solid articles containing precursor polymers with carboxylic acid groups, including PAA-based IPNs, is determined by a balance between the diffusion rate of reactants and the hydrolysis rate of coupling reagents and intermediate esters due to reaction kinetics. One class of coupling reagents that has been widely used to activate and derivatize carboxylic acids in aqueous solutions are carbodiimides. In various embodiments, an aminosulfonic acid compound, such as taurine, is first diffused into the PAA-based IPN, followed by the addition of an N-substituted carbodiimide. The N-substituted carbodiimide reacts with carboxylic acids to form highly reactive o-acylisourea intermediates that are pH-dependent and prone to hydrolysis within seconds at near physiological pH (Hoare, DG. and Koshland, DEJ. (1967) "A method for the quantitative modification and estimation of carboxylic acid groups in proteins", Journal of Biological Chemistry, 242(10), pp. 2447-2453). After hydrolysis, the intermediate ester is converted back to a carboxylic acid and an inactive N-acylurea. This intermediate hydrolysis essentially consumes the coupling reagent before it can diffuse through the entire IPN and react with the primary amine of the aminosulfonic acid compound. The hydrolysis of the intermediate ester can be reduced by lowering the pH, but the hydrolysis of the unreacted coupling reagent accelerates under acidic conditions (Gilles, MA, Hudson, AQ and Borders, CL (1990) "Stability of water-soluble carbodiimides in aqueous solution", Analytical Biochemistry. Academic Press, 184(2), pp. 244-248). Moreover, under acidic conditions, the diffusivity of the coupling reagent decreases as the IPN loses its water content and its permeability decreases. This causes the coupling reagent to be consumed on the surface of the IPN, further inhibiting the bulk reaction.In summary, molecules that are unstable in aqueous solution or that form intermediate esters that are susceptible to hydrolysis at physiological pH cannot effectively derivatize the entire PAA-based IPN, and the modification remains localized to the surface of the IPN.

[0133] Various properties of IPNs in physiological conditions, including smooth properties, depend on the bulk derivatization of the material. We have found that IPN modification beyond a certain depth can only be achieved if a) the coupling reagent is water-soluble and stable under aqueous conditions, b) the intermediate ester is stable at physiological pH, and c) the diffusion rate of the reactants is sufficient to allow reaction to occur before the intermediate ester undergoes hydrolysis. Triazine-based coupling reagents, such as CDMT or DMTMM, are stable under aqueous conditions and have been used to derivatize macrosugars, such as hyaluronan (D'este M, Eglin D, Alini M, (2014), "A systematic analysis of DMTMM vs EDC / NHS for ligation of amines to Hyaluronan in water", Carbohydrate Polymers, Vol. 108, pp. 239-246). Reactions with DMTMM, where all reactants are in solution, can have higher conversion rates than carbodiimides. In this embodiment, the reaction conditions can be adjusted to allow efficient diffusion of reactants before the intermediate ester formed between the triazine-based compound and the carboxylic acid groups of the secondary network of the IPN is hydrolyzed. Since the reaction is rate-limited by diffusion and ester hydrolysis, the depth of the reaction can be controlled by varying the pH, by varying the reaction time, by adding coupling reagents, or by a combination of any two or all three of the above. The pH allows control of the permeability of the IPN and the reactivity / hydrolysis rate of the intermediate ester. The reaction time allows control of the amount of time it takes for reactants to diffuse and react throughout the material. Control of the addition of the coupling reagent allows the coupling reagent to be added at the same rate as the overall reaction rate, coupling the diffusion and reaction of the reagent together with the hydrogel swelling. By adjusting these parameters, derivatization of the IPN can be achieved to a depth ranging from a few microns to hundreds of microns or throughout the entire depth of the material.

[0134] A number of types of initiators can be used, such as photoinitiators (e.g., phenone-containing compounds), thermal initiators, or chemical initiators. Examples of thermal initiators include, but are not limited to, azo compounds, peroxides (e.g., benzoyl peroxide), persulfates (e.g., potassium persulfate or ammonium persulfate), derivatives or combinations thereof.

[0135] Variations in crosslink identity and density (e.g., 0.0001 mol % to 25 mol % crosslinker relative to monomer), initiator concentration (e.g., 0.0001 mol % to 0 mol % relative to monomer), molecular weight of precursor polymer, relative weight percent of polymer, light wavelength (ultraviolet to visible range), light intensity (0.01 mW / cm 2 ~5 W / cm 2 ), temperature, pH and ionic strength of the swelling liquid, and hydration level.

[0136] The second network material can be synthesized without a crosslinker.

[0137] The moisture content of these materials may range between 2% and 99%.

[0138] The different components of the mixed anionic IPN can be incorporated in combination with carboxylic acid group-containing monomers (e.g., vinyl alcohol, ethylene glycol acrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, acrylamide, N-isopropylacrylamide, dimethacrylamide, and combinations or derivatives thereof). Any monomer or combination of monomers can be used with a suitable solvent, as long as the carboxylic acid group-containing monomer can be included and enter (swell) into the first polymer.

[0139] The mixed anionic IPNs can be chemically or physically incorporated into their bulk or surface with certain additives, such as antioxidants (e.g., vitamin C, vitamin E, or Santowhite powder) and / or antimicrobial agents (e.g., antibiotics). These can be chemically bound to the material, for example, by esterification of the antioxidant with any vinyl-group-containing monomer (e.g., methacrylate, acrylate, acrylamide, vinyl, or allyl ether).

[0140] More than two (eg, three or more) networks can also be formed, each of which is either crosslinked or non-crosslinked.

[0141] Other modifications will be apparent to those skilled in the art.

[0142] Further aspects of the disclosure are presented in the following paragraphs.

[0143] EMBODIMENT 1 An implant comprising an ionic polymer comprising underivatized carboxylic acid groups and aminosulfonic acid derivatized carboxylic acid groups.

[0144] EMBODIMENT 2. The implant of embodiment 1, wherein the underivatized carboxylic acid group corresponds to one or more of the following: underivatized acrylic acid monomer in the ionic polymer, underivatized methacrylic acid monomer in the ionic polymer, underivatized crotonic acid monomer in the ionic polymer, underivatized linoleic acid monomer in the ionic polymer, underivatized maleic acid monomer in the ionic polymer, and underivatized fumaric acid monomer in the ionic polymer, and the aminosulfonic acid derivatized carboxylic acid group corresponds to one or more of the following: aminosulfonic acid derivatized acrylic acid monomer in the ionic polymer, aminosulfonic acid derivatized methacrylic acid monomer in the ionic polymer, aminosulfonic acid derivatized crotonic acid monomer in the ionic polymer, aminosulfonic acid derivatized linoleic acid monomer in the ionic polymer, aminosulfonic acid derivatized maleic acid monomer in the ionic polymer, and aminosulfonic acid derivatized fumaric acid monomer in the ionic polymer.

[0145] Aspect 3: The implant comprises a measurable amount of the formula (H2N) x R(SO3H) y 3. The implant of embodiment 1 or 2, comprising an aminosulfonic acid compound of the formula: wherein R is an organic moiety, x is a positive integer, and y is a positive integer, or a salt thereof.

[0146] Embodiment 4 The implant of embodiment 3, wherein R is a hydrocarbon moiety.

[0147] Embodiment 5 The implant of embodiment 4, wherein the hydrocarbon moiety is an alkane moiety, an alkene moiety, an alkyne moiety, an aromatic moiety, or a hydrocarbon moiety having a combination of two or more of alkane, alkene, alkyne, and aromatic substituents.

[0148] Embodiment 6 The implant of embodiment 4 or 5, wherein the hydrocarbon moiety is a C1 to C12 hydrocarbon moiety.

[0149] Embodiment 7 The implant of embodiment 1 or 2, wherein the implant comprises a measurable amount of an aminosulfonic acid compound selected from taurine and taurine derivatives.

[0150] Embodiment 8 The implant of any of embodiments 1 to 7, wherein the concentration of underivatized carboxylic acid groups and the concentration of aminosulfonic acid derivatized carboxylic acid groups are substantially constant throughout the implant.

[0151] Embodiment 9 The implant of any of embodiments 1 to 7, wherein the concentration of underivatized carboxylic acid groups and / or the concentration of aminosulfonic acid derivatized carboxylic acid groups varies by at least + / - 10% between two points within the implant.

[0152] Embodiment 10 The implant of any of embodiments 1 to 7, wherein the implant comprises a gradient concentration of underivatized carboxylic acid groups and / or a gradient concentration of aminosulfonic acid derivatized carboxylic acid groups.

[0153] Embodiment 11 The implant of embodiment 10, wherein the concentration of underivatized carboxylic acid groups decreases with increasing distance from at least one exterior surface of the implant.

[0154] Embodiment 12 The implant of embodiment 10, wherein the concentration of underivatized carboxylic acid groups increases with increasing distance from at least one exterior surface of the implant.

[0155] Embodiment 13 The implant of any of embodiments 10 to 12, wherein the concentration of aminosulfonic acid-derivatized carboxylic acid groups decreases with increasing distance from at least one exterior surface of the implant.

[0156] Embodiment 14 The implant of any of embodiments 10 to 12, wherein the concentration of aminosulfonic acid derivatized carboxylic acid groups increases with increasing distance from at least one exterior surface of the implant.

[0157] Embodiment 15 The implant of any of embodiments 1 to 14, wherein the molar ratio of aminosulfonic acid derivatized carboxylic acid groups to underivatized carboxylic acid groups in the implant varies by at least + / - 10% between any two points.

[0158] Embodiment 16 The implant of any of embodiments 1 to 14, wherein the molar ratio of aminosulfonic acid derivatized carboxylic acid groups to underivatized carboxylic acid groups in the implant decreases with increasing distance from at least one exterior surface of the implant.

[0159] Embodiment 17 The implant of any of embodiments 1 to 14, wherein the molar ratio of aminosulfonic acid derivatized carboxylic acid groups to underivatized carboxylic acid groups in the implant increases with increasing distance from at least one exterior surface of the implant.

[0160] Embodiment 18 The implant of any of embodiments 1 to 14, wherein the molar ratio of aminosulfonic acid derivatized carboxylic acid groups to underivatized carboxylic acid groups varies between at least one surface of the implant and an opposing surface of the implant.

[0161] Example 19. The implant of any of the preceding examples, wherein the implant comprises an interpenetrating or semi-interpenetrating polymer network comprising a first polymer network comprising a first polymer and a second polymer network comprising an ionic polymer.

[0162] Embodiment 20. The implant of embodiment 19, wherein the first polymer is a hydrophobic polymer.

[0163] Embodiment 21 The implant of embodiment 19 or 20, wherein the first polymer is a thermoplastic polymer.

[0164]

[0031] Embodiment 22. The implant of any of embodiments 19 to 21, wherein the first polymer is a polyurethane.

[0165] Embodiment 23 The implant of embodiment 22, wherein the polyurethane is a polyether urethane.

[0166]

[0031] Embodiment 24. The implant of any of embodiments 1 to 23, wherein the implant is configured to repair or replace cartilage in a joint within the body.

[0167] Aspect 25: The implant of aspect 24, wherein the joint in the body is selected from a knee joint, condyle, patella, tibial plateau, ankle joint, elbow joint, shoulder joint, finger joint, thumb joint, glenoid cavity, hip joint, intervertebral disc, facet joint, labrum, meniscus, metacarpal joint, metatarsal joint, toe joint, temporomandibular joint, and wrist joint (including portions thereof).

[0168] Embodiment 26. A method comprising the step of reacting a solid article comprising a precursor polymer comprising underivatized carboxylic acid groups with an aminosulfonic acid compound, thereby forming an amide bond between the carboxylic acid group of the precursor polymer and the amine group of the aminosulfonic acid compound.

[0169] Aspect 27: The aminosulfonic acid compound is represented by the formula (H2N) x R(SO3H) yor a salt thereof, wherein R is an organic moiety, x is a positive integer, and y is a positive integer.

[0170] Embodiment 28 The method of embodiment 26, wherein R is a hydrocarbon moiety.

[0171]

[0041] Embodiment 29. The method of embodiment 28, wherein the hydrocarbon moiety is an alkane moiety, an alkene moiety, an alkyne moiety, and an aromatic moiety, or a hydrocarbon moiety that includes a combination of two or more of an alkane, alkene, alkyne, or aromatic substituent.

[0172] Embodiment 30 The method of embodiment 28 or 29, wherein the hydrocarbon moiety is a C1 to C12 hydrocarbon moiety.

[0173] The method of embodiment 26, wherein the aminosulfonic acid is selected from taurine and taurine derivatives.

[0174]

[0036] Embodiment 32. The method of any of embodiments 26 to 31, comprising contacting the solid article with an aminosulfonic acid compound, thereby causing the aminosulfonic acid compound to diffuse into the solid article.

[0175] Embodiment 33. The method of embodiment 32, further comprising the step of contacting the solid article with a coupling reagent, thereby causing the coupling reagent to diffuse into the solid article.

[0176]

[0046] Embodiment 34. The method of embodiment 33, wherein the coupling reagent is diffused into the solid article before the sulfonic acid compound is diffused into the solid article, the coupling reagent is diffused into the solid article after the sulfonic acid compound is diffused into the solid article, or the coupling reagent and the sulfonic acid compound are diffused into the solid article simultaneously.

[0177] Aspect 35 The method of aspect 33 or 34, wherein the coupling reagent is selected from triazine-based coupling reagents, carbodiimide coupling reagents, phosphonium salt coupling reagents, aminium salt coupling reagents, and fluoroformamidinium coupling reagents.

[0178] Aspect 36 The method of aspect 33 or 34, wherein the coupling reagent is 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM).

[0179] Example 37 The method of any of examples 26 to 36, wherein the precursor polymer is selected from a polymer comprising one or more monomers selected from acrylic acid, methacrylic acid, crotonic acid, linoleic acid, maleic acid, and fumaric acid.

[0180]

[0046] Example 38. The method of any of examples 26 to 37, wherein the solid article comprises an interpenetrating or semi-interpenetrating polymer network comprising a first polymer network comprising the first polymer and a second polymer network comprising the precursor polymer.

[0181] Embodiment 39 The method of embodiment 38, wherein the first polymer is a hydrophobic polymer.

[0182]

[0046] Example 40. The method of example 38 or 39, wherein the first polymer is a thermoplastic polymer.

[0183]

[0046] Embodiment 41 The method of any of embodiments 38 to 40, wherein the first polymer is a polyurethane.

[0184]

[0046] Embodiment 42. The method of embodiment 41, wherein the polyurethane is a polyether urethane.

[0185]

[0046] Embodiment 43. The method of any of embodiments 26 to 42, wherein the implant is configured to repair or replace cartilage in a joint within the body.

[0186] Aspect 44: The method of aspect 43, wherein the joint in the body is selected from a knee joint, condyle, patella, tibial plateau, ankle joint, elbow joint, shoulder joint, finger joint, thumb joint, glenoid cavity, hip joint, intervertebral disc, facet joint, labrum, meniscus, metacarpal joint, metatarsal joint, toe joint, temporomandibular joint, and wrist joint (including portions thereof).

[0187] Embodiment 45. An implant comprising an ionic polymer and a divalent cation-containing solution comprising one or more divalent metal cations, wherein the implant is at least partially immersed in the divalent cation-containing solution.

[0188]

[0081] Embodiment 46. The implant of embodiment 45, wherein the implant and the divalent cation-containing solution are contained within a sterile package.

[0189]

[0081] Embodiment 47. The implant of any of embodiments 44 to 46, wherein the divalent cation-containing solution is a simulated body fluid containing physiological levels of ions present in synovial fluid.

[0190] Embodiment 48. The implant of any of embodiments 44 to 47, wherein the divalent cation-containing solution comprises 0.1 to 5 mM total divalent metal cations.

[0191] Embodiment 49. The implant of any of embodiments 44 to 48, wherein the divalent cation-containing solution comprises calcium ions, magnesium ions, or a combination of calcium ions and magnesium ions.

[0192] Embodiment 50. The implant of any of embodiments 44 to 48, wherein the divalent cation-containing solution comprises calcium ions and magnesium ions.

[0193] Embodiment 51 The implant of embodiment 50, wherein the divalent cation-containing solution comprises 0.5 to 2.0 mM calcium ions.

[0194] Embodiment 52. The implant of embodiment 50 or 51, wherein the divalent cation-containing solution comprises 0.2 to 1.5 mM magnesium ions.

[0195]

[0046] Embodiment 53. The implant of any of embodiments 44 to 52, wherein the divalent cation-containing solution further comprises monovalent metal ions selected from sodium ions, potassium ions, or a combination of sodium ions and potassium ions.

[0196] Embodiment 54. The implant of embodiment 53, wherein the divalent cation-containing solution contains 0-300 mM total monovalent metal cations.

[0197] Embodiment 55 The implant of any of embodiments 44 to 54, wherein the ionic polymer comprises carboxylic acid groups, sulfonic acid groups, or a combination of carboxylic acid groups and sulfonic acid groups.

[0198]

[0046] Embodiment 56. The implant of any of embodiments 44 to 54, wherein the ionic polymer comprises carboxylic acid groups and sulfonic acid groups.

[0199]

[0046] Example 57. The implant of any of examples 44 to 56, wherein the implant comprises an interpenetrating or semi-interpenetrating polymer network comprising a first polymer network comprising a first polymer and a second polymer network comprising an ionic polymer.

[0200] Embodiment 58. The implant of embodiment 57, wherein the first polymer is a hydrophobic polymer.

[0201]

[0046] Embodiment 59. The implant of embodiment 57 or 58, wherein the first polymer is a thermoplastic polymer.

[0202] Embodiment 60. The implant of any of embodiments 57 to 59, wherein the first polymer is a polyurethane.

[0203] Embodiment 61 The implant of embodiment 60, wherein the polyurethane is a polyether urethane.

[0204] Embodiment 62. The implant of any of embodiments 44 to 61, wherein the implant is selected to repair or replace cartilage in a joint within the body.

[0205] Embodiment 63: The implant of embodiment 62, wherein the joint is selected from a knee joint, a condyle, a patella, a tibial plateau, an ankle joint, an elbow joint, a shoulder joint, a finger joint, a thumb joint, a glenoid cavity, a hip joint, an intervertebral disc, a facet joint, a labrum, a meniscus, a metacarpal joint, a metatarsal joint, a toe joint, a temporomandibular joint, and a wrist joint (including portions thereof).

[0206] [Example] [Example 1] The following description refers to a first exemplary embodiment of an interpenetrating ionic polymer composition having polyetherurethane as a first network and polyacrylic acid as a second polymer network. The IPN is synthesized in two sequential steps. A test article made of polyetherurethane is immersed in an aqueous solution of 70% (w / w%) acrylic acid supplemented with 5000 ppm N,N'-methylenebis(acrylamide) and 1000 ppm 2-hydroxy-2-methylpropiophenone. The swollen article is exposed to UV radiation (40 mW / cm2). 2) for 13 min and then neutralized at a constant pH=7.4. The final composition of the IPN contained 37 / 19 / 45 (wt%) PEU, PAA and HO, respectively. The test article was incubated in taurine (aminoethanesulfonic acid) solution (320 mM) for 1 day, after which an equimolar amount of DMTMM ((4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methyl-morpholinium chloride)) was added. The test article was left to react for 48 h, and it was washed with copious amounts of water for 4 days. This process is illustrated diagrammatically in FIG. 2. After synthesis, the chemical composition was assessed by elemental analysis (Table 1). The yield of sulfonation of PAA was 50%. Moreover, as shown in FIG. 4, the penetration of the amidation reaction reached half (50%) of the entire thickness of the test article (i.e., 2 mm thick sample) or 1000 microns. In other words, when both sides are involved in the diffusion of the reagent, the conversion reaches 100% and the material is functionalized throughout the thickness of the PAA-PEU network. In contrast, when a carbodiimide such as EDC is used under identical reaction conditions and reactant ratios, the penetration and functionalization of the PAA-PEU network does not exceed 20% or a depth of 400 microns in a 2 mm thick sample. The difference in coupling efficiency between EDC and triazine coupling reagents has also been reported previously in the functionalization of hyaluronan macropolymers in aqueous conditions (D'este M, Eglin D, Alini M, (2014), "A systematic analysis of DMTMM vs EDC / NHS for ligation of amines to Hyaluronan in water", Carbohyrate Polymers, Vol. 108, pp. 239-246).

[0207] The following description refers to a second exemplary embodiment of an interpenetrating ionic polymer composition having polyetherurethane as a first network and polyacrylic acid as a second polymer network. The IPN is synthesized in two sequential steps. A test article made of polyetherurethane is immersed in an aqueous solution of 60% (w / w%) acrylic acid supplemented with 5000 ppm N,N'-methylenebis(acrylamide) and 1000 ppm 2-hydroxy-2-methylpropiophenone. The swollen article is exposed to UV radiation (40 mW / cm2). 2 ) for 13 min and then neutralized at a constant pH=7.4. The final composition of the IPN contained 48 / 17 / 35 (wt%) PEU, PAA and HO, respectively. The test article was incubated in taurine solution (320 mM) for 1 day, after which an equimolar amount of DMTMM was added. The test article was left to react for 48 h and was washed with copious amounts of water for 4 days. After synthesis, the chemical composition was assessed by elemental analysis (Table 1). The yield of sulfonation of PAA was 29%.

[0208] The following description refers to a third exemplary embodiment of an interpenetrating ionic polymer composition having polyetherurethane as a first network and polyacrylic acid as a second polymer network. The IPN is synthesized in two sequential steps. A test article made of polyetherurethane is immersed in an aqueous solution of 50% (w / w%) acrylic acid supplemented with 2000 ppm N,N'-methylenebis(acrylamide) and 2000 ppm 2-hydroxy-2-methylpropiophenone. The swollen article is exposed to UV radiation (40 mW / cm2). 2 ) for 13 min and then neutralized at a constant pH=7.4. The final composition of the IPN contained 57 / 16 / 26 (wt%) PEU, PAA and HO, respectively. The test article was incubated in taurine solution (320 mM) for 1 day, after which an equimolar amount of DMTMM was added. The test article was left to react for 48 h, and it was washed with copious amounts of water for 4 days. After synthesis, the chemical composition was assessed by elemental analysis (Table 1). The yield of sulfonation of PAA was 26%.

[0209] [Table 1]

[0210] [Example 2] Gradient PEU-PAA blends with PAA / PEU (w / w%) contents ranging from 17.6% to 29.9% were synthesized by the following procedure along the lines described in Example 1. There is a linear correlation between the AA soaking solution and PAA / PEU (w / w%), allowing for the determination of the final PAA / PEU percentage based on the initial soaking solution. The results are shown in Table 2.

[0211] [Table 2]

[0212] The gradient PEU-PAA blends were then sulfonated following a procedure along the lines of Example 1. Percent sulfonation was characterized by increasing dry and wet weights along with elemental analysis to calculate sulfur content and sulfonation conversion. The data are summarized in Table 3. The sulfur content ranged from 0.5-2% and the sulfonation conversion ranged from 9% to 31%.

[0213] [Table 3]

[0214] The sulfonated gradient PEU-PAA materials showed a trend of higher weight gain after sulfonation with increasing PAA / PEU w / w%, suggesting that as the PAA content increases, more carboxyl groups of PAA react with taurine to introduce sulfonate groups. The weight gain (both wet and dry weight) of the sulfonated gradient PEU-PAA was found to be linear as a function of PAA / PEU content. The dry weight gain could be a result of the addition of taurine molecules to the PAA backbone through the sulfonation reaction, while the wet weight gain could be attributed to the ability of the sulfonated gradient PEU-PAA to retain moisture content.

[0215] Elemental analysis was performed to determine the carbon, nitrogen, hydrogen, and sulfur content of the sulfonated test articles. This data was used to calculate the conversion of carboxyl groups to sulfonate groups. As can be seen in Table 3, the sulfur content / sulfonation conversion increased with increasing PAA / PEU percentage. This indicates that more taurine can be bound with increasing number of carboxyl groups per unit weight.

[0216] The final synthesis step of the sulfonated gradient PEU-PAA test article was performed by incubating the test article in simulated body fluid (SBF, 1.2 mM Ca) prior to gamma irradiation. 2+ , 0.6 mM Mg 2+ Equilibration in SBF (154 mM NaCl) was required. The final compositions of all synthesized materials after SBF equilibration were calculated and are listed in Table 4 (highlighted in grey).

[0217] [Table 4]

[0218] The tensile, compressive, and tear properties of sulfonated gradient PEU-PAA test articles across a range of PAA contents were evaluated. The data are summarized in Tables 5 through 7. To allow for direct comparison of material properties between gradient PEU-PAA and non-sulfonated gradient PEU-PAA formulations using a common variable, the PAA / PEU percentage is used as the independent variable for the following reasons: (a) the same sulfonation conditions were used for all synthesized materials regardless of their PAA / PEU (w / w%), (b) sulfonation was indirectly controlled by the level of PAA / PEU (w / w%) (see Table 3), and (c) materials synthesized under the same initial conditions had statistically similar mechanical properties regardless of the sulfonation process or sulfur content.

[0219] The tensile properties of all the formulations are listed in Table 5 and Table 5.1. The ultimate tensile strength (UTS) was found to decrease with increasing PAA / PEU w / w%. This is attributed to the increase in moisture content as a function of PAA / PEU w / w% (Table 3), resulting in a weaker material.

[0220] [Table 5]

[0221] [Table 6]

[0222] Similar trends were observed for all other tensile properties evaluated. Specifically, the ultimate true strain, which captures the maximum elongation of the material before failure, decreased with PAA / PEU w / w%, ranging from 223.8±52.3% for the formulation with the lowest PAA / PEU w / w% (17.6%) to 95.2±12.8% for the formulation with the highest (40.7%) (Table 5.1). The ultimate true strain for the non-sulfonated gradient PEU-PAA was 181.0±32.7%, which is almost two times higher than its sulfonated counterpart (95.2±12.8%) with the same PAA / PEU w / w%. This is due to the sulfonated gradient PEU-PAA formulation with 40.7% PAA / PEU w / w% having more water (41.4%--see Table 3) than the non-sulfonated gradient PEU-PAA (36.7%--see Table 3). Moreover, large variations in ultimate true strain were observed due to the randomness of material failure under tension influenced by imperfections in the material and the test article.

[0223] The tensile modulus (Young's modulus), which defines the relationship between stress and strain in the linear elastic region, decreased exponentially with increasing PAA / PEU w / w%. The tensile modulus of the blend with (highest) PAA / PEU w / w% of 40.7 (32.5±0.8 MPa) was significantly decreased (p<0.01) from the previous blend with 30% PAA / PEU w / w% (48.4±2.8 MPa), suggesting that above this threshold, the tensile modulus decreases rapidly. Moreover, similar to the trends seen in the ultimate tensile strength and tensile strain, the tensile modulus of the non-sulfonated gradient PEU-PAA was higher (46.4±2.3) than that of the sulfonated gradient PEU-PAA with the same PAA / PEU w / w%.

[0224] Similar to UTS, the tangential tensile modulus at 30% strain (see Table 5.1), useful in describing the behavior of materials stressed beyond the elastic range to plastic deformation, decreased with increasing PAA / PEU w / w%. The tangential tensile modulus of the test article with the lowest PAA / PEU w / w% (17.6%) was 37.1 ± 2.2 MPa, decreasing to 24.6 ± 0.5 MPa for the formulation with the highest PAA / PEU w / w% (40.7%). In contrast, the tangential tensile modulus of the non-sulfonated gradient PEU-PAA was 29.0 ± 0.35 MPa, indicating that both sulfonated and non-sulfonated formulations with the same PAA / PEU w / w% have similar deformation rates when the material is plastically deformed.

[0225] To summarize all the tensile properties, lower levels of PAA can be used for the sulfonated gradient PEU-PAA compared to the non-sulfonated gradient PEU-PAA to obtain similar tensile properties to the non-sulfonated gradient PEU-PAA.

[0226] The compression properties of all the formulations are listed in (Table 6) and (Table 6.1). The ultimate compressive strength of all the formulations was above the desired preliminary specification of 25.4 MPa. All the sulfonated gradient PEU-PAA samples did not break under compression even at high strains (greater than 60% compressive true strain). No specific trends were established for the ultimate compressive strength and ultimate compressive strain as the materials did not break under compression.

[0227] [Table 7]

[0228] [Table 8]

[0229] The compressive strength of the non-sulfonated gradient PEU-PAA was 332.8±16.7 MPa, higher than all of the sulfonated gradient PEU-PAA formulations. A direct comparison of compressive strengths was not possible because the materials did not break under compression, therefore the materials were re-evaluated under dynamic compression.

[0230] The compressive modulus (Young's modulus in compression), which measures the stiffness of a solid material under compression in the linear elastic range, showed an exponential decrease with increasing PAA / PEU w / w%, similar to the tensile modulus. The compressive modulus gradually decreased from 111.1 ± 11.5 MPa for the formulation with the lowest PAA / PEU w / w% (17.6) to 50.4 ± 10.6 MPa for the formulation with the highest PAA / PEU w / w% (40.7). These values ​​are in the same order of magnitude as those for human articular cartilage, ranging from 8.1 to 15.3 MPa (Parsons, JR (1998), "Cartilage", in Handbook of Biomaterial Properties. Boston, MA: Springer US, pp. 40-47. doi: 10.1007 / 978-1-4615-5801-9_4), indicating that the sulfonated formulations have comparable physiological stiffness.

[0231] Similar to the tangential tensile modulus, the tangential compressive modulus demonstrates the behavior of a material beyond the elastic region and the rate at which the material undergoes plastic deformation. The tangential compressive modulus was 177.8±8.7 MPa for the test article with the lowest PAA / PEU w / w% (17.6%), decreasing to 145.7±19.5 MPa for the formulation with the highest PAA / PEU w / w% (40.7%). The tangential compressive modulus of the non-sulfonated gradient PEU-PAA was 155.9±4.3, corresponding to the sulfonated material with lower PAA / PEU w / w% or higher PEU content.

[0232] The tear strength followed a similar trend as the tensile and compressive properties, decreasing with increasing PAA / PEU w / w% (Table 7). Tear strength values ​​obtained for the range of sulfonated gradient PEU-PAA synthesized ranged from 28.8 ± 2.2 N / mm to 70 ± 3.8 N / mm, respectively. The tear strength of the non-sulfonated gradient PEU-PAA was 57.7 ± 2.5 N / mm, similar to sulfonated materials with lower PAA / PEU w / w% or higher PEU content.

[0233] [Table 9]

[0234] As part of the synthesis, all formulations containing non-sulfonated gradient PEU-PAA were equilibrated in SBF prior to packaging and gamma irradiation. The coefficient of friction (COF) values ​​are listed in Table 8. It was observed that all sulfonated gradient PEU-PAA demonstrated similar friction values ​​(0.034±0.007) regardless of PAA / PEU content and sulfur content, which were significantly lower (p<0.01) compared to non-sulfonated gradient PEU-PAA.

[0235] An initial assessment of the sulfonation distribution throughout the thickness of the material demonstrated that the sulfonation was more abundant at the bearing surface than in the bulk, gradually decreasing with increasing depth as can be seen in Figure 4 (sulfonated gradient PEU-PAA formulation with 48.1 wt% PEU, 14.4 wt% PAA, 37.4 wt% water). The extent of sulfonation was measured using Raman spectroscopy at 1640 cm -1 Carbonyl peak at 1045 cm -1 The intensity of the sulfonate peak is determined by measuring the normalized intensity of the sulfonate peak.

[0236] Since the sulfonation reaction conditions were the same for all sulfonated materials, it is assumed that all sulfonated gradient PEU-PAA formulations have the highest concentration of sulfonate moieties on the bearing surface, regardless of their PAA / PEU percentages. In contrast, the non-sulfonated gradient PEU-PAA equilibrated in SBF exhibited a friction coefficient above 0.1, suggesting that the sulfonation process results in a lubricious material with a low friction coefficient.

[0237] [Table 10]

[0238] The coefficient of friction for a sulfonated gradient PEU-PAA group with similar PAA / PEU w / w% (22.9%) and sulfur content (1.05%) was also assessed. The coefficient of friction for this formulation was 0.042 ± 0.001 (n = 3).

[0239] Thus, the effect of a range of PAA / PEU percentages from 17.6% to 40.7% and sulfonation conversions from 9 to 31% on mechanical and frictional properties was assessed. Formulations were compared to a non-sulfonated gradient PEU-PAA formulation (40.7% PAA / PEU and no sulfonation) to evaluate the effect of sulfonation on properties. All IPNs had mechanical properties that met or exceeded current preliminary specifications. Formulations with lower PAA / PEU w / w% were stiffer than those with higher PAA / PEU w / w%, an effect attributed to the increased water content after sulfonation.

[0240] All sulfonated formulations had a lower coefficient of friction (COF) in SBF (<0.045) compared to the non-sulfonated gradient PEU-PAA (0.1), indicating that the lubricity of the surface was independent of the % sulfonation over the range of 9-31% tested. All sulfonated formulations showed similar COF values, suggesting that the % sulfonation or PAA content over the range tested was sufficient to create a highly lubricious surface in the presence of SBF.

[0241] To further test the ability of the sulfonated formulation of Example 3 to resist the effects of divalent ions under physiological conditions, a test was developed to quantify water loss over a broad physiological range of total divalent ion concentrations. This test, reported in Ising, H., Bertschat, F., Gunther, T., Jeremias, E., Jeremias, A. and Ising, H. (1995) "Measurement of Free Magnesium in Blood, Serum and Plasma with an Ion-Sensitive Electrode", Clinical Chemistry and Laboratory Medicine, 33(6), 365-372 and Fijorek, K., Puskulluoglu, M., Tomaszewska, D., Tomaszewski, R., Glinka, A. and Polak, S. (2014) "Serum potassium, sodium and calcium levels in healthy individuals - literature review and data analysis", Folia Medica Cracoviensia54(1), 53-70, is used to determine the sensitivity of materials within the low and high physiological ranges by monitoring the percentage of water loss per mM of divalent ions. Sulfonated gradient PEU-PAA and non-sulfonated gradient PEU-PAA test articles equilibrated in SBF (1.8 mM total divalent cations) were placed in buffers ranging from 1.4 mM (low physiological range) to 2.2 mM (high physiological range) of total divalent ions and their water loss was measured after equilibration. Lines were fitted to each concentration and the slope of each line calculated (Table 9). The divalent ion sensitivity (slope of the fitted line) of a representative set of test formulations is depicted (Figures 3A-3E). Sensitivity ranged from -1.32% / mM (% water loss per millimole of total divalent cations) for a formulation with 17.6% PAA / PEU w / w% to -1.86% / mM for a formulation with 40.7% PAA / PEU w / w%.

[0242] [Table 11]

[0243] One desirable property of a synthetic cartilage implant is the ability of the material to maintain its water content at physiological conditions. When implanted in the human body, the device, packaged in phosphate buffered saline, adapts to the divalent ion-rich environment of synovial fluid (approximately 1.2 mM Ca). +2 , 0.6 mM Mg +2 ) The sodium salts of polymeric weak acids such as PAA are exposed to Ca +2 and Mg +2 It is known that they have high selectivity for Ca, which ultimately leads to the transfer of sodium ions (Dorfner, K. (1991) "Ion exchangers", Berlin, New York: DE GRUYTER. doi: 10.1515 / 9783110862430). +2 and Mg +2 Since one molecule of PAA can bind to two carboxylate groups, the PAA chains can be crosslinked through ionic interactions, which leads to the contraction of the PAA network and thus water loss in vivo.

[0244] In this example, all sulfonated gradient PEU-PAA formulations exposed to SBF exhibited less water loss after equilibration than the non-sulfonated gradient PEU-PAA. Moreover, water loss was further minimized within the range of PAA / PEU percentages with comparable mechanical properties to the non-sulfonated gradient PEU-PAA. In particular, sulfonated formulations with PAA / PEU w / w% in the range of 25.5-30% and / or sulfonation levels of 21-31% exhibited less water loss (6.5±0.6-9.2±0.5%) than the non-sulfonated gradient PEU-PAA (13.8±1.0) and no measurable change in weight loss over the range of physiological ionic variations tested. The following are examples of embodiments of the present invention. [Embodiment 1] 1. An orthopedic implant comprising a crosslinked ionic polymer comprising sulfonic acid derivatized groups, the sulfonic acid derivatized groups being present on a surface of the implant and extending from the surface into the bulk of the implant a distance of at least 500 microns. [Embodiment 2] The orthopedic implant of embodiment 1, wherein the sulfonic acid derivatized group is an aminosulfonic acid derivatized group. [Embodiment 3] The formula for the amount of implant that can be measured (H 2 N) x R(SO 3 H) y 3. The orthopedic implant of embodiment 2, comprising an aminosulfonic acid compound of the formula: or a salt thereof, wherein R is an organic moiety, x is a positive integer, and y is a positive integer. [Embodiment 4] The orthopedic implant of embodiment 3, wherein R is a hydrocarbon moiety. [Embodiment 5] The orthopedic implant of embodiment 4, wherein the hydrocarbon moiety is an alkane moiety, an alkene moiety, an alkyne moiety, an aromatic moiety, or a hydrocarbon moiety having a combination of two or more of alkane, alkene, alkyne, and aromatic substituents. [Embodiment 6] The hydrocarbon portion is C 1 ~C 12 The orthopedic implant of embodiment 4, wherein the moiety is a hydrocarbon moiety. [Embodiment 7] 3. The orthopedic implant of embodiment 2, wherein the implant comprises a measurable amount of an aminosulfonic acid compound selected from taurine and taurine derivatives. [Embodiment 8] The orthopedic implant of embodiment 1-7, wherein the sulfonic acid derivatized group is a sulfonic acid derivatized carboxylic acid group. [Embodiment 9] The orthopedic implant of embodiment 8, wherein the crosslinked ionic polymer further comprises underivatized carboxylic acid groups. [Embodiment 10] 10. The orthopedic implant of embodiment 9, wherein the underivatized carboxylic acid groups correspond to one or more of the following: underivatized acrylic acid polymerized monomers in an ionic polymer, underivatized methacrylic acid polymerized monomers in an ionic polymer, underivatized crotonic acid polymerized monomers in an ionic polymer, underivatized linoleic acid polymerized monomers in an ionic polymer, underivatized maleic acid polymerized monomers in an ionic polymer, and underivatized fumaric acid polymerized monomers in an ionic polymer; and the aminosulfonic acid derivatized carboxylic acid groups correspond to one or more of aminosulfonic acid derivatized acrylic acid polymerized monomers in an ionic polymer, aminosulfonic acid derivatized methacrylic acid polymerized monomers in an ionic polymer, aminosulfonic acid derivatized crotonic acid polymerized monomers in an ionic polymer, aminosulfonic acid derivatized linoleic acid polymerized monomers in an ionic polymer, aminosulfonic acid derivatized maleic acid polymerized monomers in an ionic polymer, and aminosulfonic acid derivatized fumaric acid polymerized monomers in an ionic polymer. [Embodiment 11] The orthopedic implant of any one of the preceding embodiments, wherein the implant comprises a concentration gradient of sulfonic acid derivatized groups. [Embodiment 12] The orthopedic implant of any one of the preceding embodiments, wherein the sulfonic acid derivatized groups extend into the bulk of the implant for a distance of at least 1 mm. [Embodiment 13] The orthopedic implant of any one of the preceding embodiments, wherein the sulfonic acid derivatized groups are present through greater than 20% of the thickness of the implant. [Embodiment 14] The orthopedic implant of any one of the preceding embodiments, wherein the sulfonic acid derivatized groups are present through greater than 50% of the thickness of the implant. [Embodiment 15] The orthopedic implant of any one of the preceding embodiments, wherein the sulfonic acid derivatized groups are present throughout greater than 75% of the thickness of the implant. [Embodiment 16] The orthopedic implant of any one of the preceding embodiments, wherein the sulfonic acid derivatized groups are present through 100% of the thickness of the implant. [Embodiment 17] The orthopedic implant of any one of the preceding embodiments, wherein the concentration of sulfonic acid derivatized groups is reduced by at least 10% from a point on the surface of the implant to at least one point in the bulk of the implant. [Embodiment 18] The orthopedic implant of embodiments 1 to 10, wherein the concentration of sulfonic acid derivatized groups does not vary by more than + / - 10% between any two points within the implant. [Embodiment 19] The orthopedic implant of embodiment 9 or 10, wherein the concentration of sulfonate-derivatized carboxylic acid groups and the concentration of underivatized carboxylic acid groups do not vary by more than + / - 10% between any two points within the implant. [Embodiment 20] 11. The orthopedic implant of embodiment 9 or 10, wherein the implant comprises a gradient concentration of sulfonate-derivatized carboxylic acid groups and a gradient concentration of said underivatized carboxylic acid groups. [Embodiment 21] The orthopedic implant of embodiments 9, 10 and 20, wherein the concentration of sulfonate derivatized carboxylic acid groups decreases by at least 10% from a point on the surface of the implant to at least one point in the bulk of the implant, and the concentration of underivatized carboxylic acid groups increases by at least 10% from a point on the surface of the implant to at least one point in the bulk of the implant. [Embodiment 22] The orthopedic implant of embodiments 9, 10 and 20, wherein the molar ratio of sulfonate-derivatized carboxylic acid groups to underivatized carboxylic acid groups is decreased by at least 10% from a point on the surface of the implant to at least one point in the bulk of the implant. [Embodiment 23] 23. The orthopedic implant of any one of the preceding embodiments, wherein the implant comprises an interpenetrating or semi-interpenetrating polymer network comprising a first polymer network comprising a first polymer and a second polymer network comprising an ionic polymer. [Embodiment 24] The orthopedic implant of embodiment 23, wherein the first polymer is a hydrophobic polymer. [Embodiment 25] The orthopedic implant of embodiment 23 or 24, wherein the first polymer is a thermoplastic polymer. [Embodiment 26] The orthopedic implant of any one of embodiments 23 to 25, wherein the first polymer is a polyurethane. [Embodiment 27] 27. The orthopedic implant of any one of embodiments 23 to 26, having a first and a second surface, the first surface having a composition corresponding to the first polymer, and wherein the concentration of sulfonic acid derivatized groups is greatest at the second surface and decreases to zero or substantially zero in the bulk of the implant. [Embodiment 28] The orthopedic implant of any one of the preceding embodiments, wherein the orthopedic implant has a weight change of less than 10% per mM change in total divalent cation concentration. [Embodiment 29] 28. The orthopedic implant of any one of the preceding embodiments, wherein the orthopedic implant has a weight change of less than 10% per mM change in total divalent cation concentration over a total divalent cation concentration range of about 0.1 mM to about 5 mM. [Embodiment 30] 28. The orthopedic implant of any of the preceding embodiments, wherein the orthopedic implant has a weight change of less than 10% per mM change in total divalent cation concentration over a physiological total divalent cation concentration range of about 1.4 mM to about 2.2 mM. [Embodiment 31] The orthopedic implant of any one of the preceding embodiments, wherein the orthopedic implant maintains a coefficient of friction of less than 0.1 over a total divalent cation concentration range of about 0.1 mM to about 5 mM. [Embodiment 32] The orthopedic implant of any one of the preceding embodiments, wherein the orthopedic implant maintains a coefficient of friction of less than 0.1 over a physiological total divalent cation concentration range of about 1.4 mM to about 2.2 mM. [Embodiment 33] 33. The orthopedic implant of embodiment 1-32, wherein the implant is configured to repair or replace cartilage in a joint within the body. [Embodiment 34] The orthopedic implant of embodiment 33, wherein the joint in the body is selected from the knee joint, condyle, patella, tibial plateau, ankle joint, elbow joint, shoulder joint, finger joint, thumb joint, glenoid cavity, hip joint, intervertebral disc, facet joint, labrum, meniscus, metacarpal joint, metatarsal joint, toe joint, temporomandibular joint, and wrist joint (including portions thereof). [Embodiment 35] A packaged article comprising the orthopedic implant of embodiments 1 to 34 contained within a sterile package. [Embodiment 36] 36. A packaged article comprising the orthopedic implant of embodiments 1-35 contained within a sterile package and a divalent cation-containing solution comprising one or more divalent metal cations. [Embodiment 37] 1. An interpenetrating or semi-interpenetrating polymer network comprising a first polymer and a second polymer network comprising a crosslinked ionic polymer comprising sulfonic acid derivatized groups, wherein the sulfonic acid derivatized groups are present on a surface of the interpenetrating or semi-interpenetrating polymer network and extend into the interpenetrating or semi-interpenetrating polymer network a distance of at least 500 microns. [Embodiment 38] 38. The interpenetrating or semi-interpenetrating polymer network of embodiment 37, wherein the sulfonic acid derivatized groups are aminosulfonic acid derivatized groups. [Embodiment 39] 38. The interpenetrating or semi-interpenetrating polymer network of embodiment 37, wherein the sulfonic acid derivatized groups are sulfonic acid derivatized carboxyl groups. [Embodiment 40] The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 39, wherein the crosslinked ionic polymer further comprises underivatized carboxylic acid groups. [Embodiment 41] The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 40, wherein the first polymer is a hydrophobic polymer. [Embodiment 42] The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 41, wherein the first polymer is a thermoplastic polymer. [Embodiment 43] The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 42, wherein the first polymer is a polyurethane. [Embodiment 44] The interpenetrating or semi-interpenetrating polymer network of embodiment 43, wherein the polyurethane is a polyether urethane. [Embodiment 45] 45. An interpenetrating or semi-interpenetrating polymer network as claimed in any one of embodiments 37 to 44, having a first and a second surface, the first surface having a composition corresponding to the first polymer, and wherein the concentration of sulfonic acid derivatized groups is greatest at the second surface and decreases to a zero or substantially zero concentration in the bulk of the interpenetrating or semi-interpenetrating polymer network. [Embodiment 46] 42. The interpenetrating or semi-interpenetrating polymer network of embodiment 41, wherein the hydrophobic polymer is a polyurethane and at least a portion of the underivatized carboxylic acid groups correspond to underivatized acrylic acid polymerized monomers in the ionic polymer. [Embodiment 47] 47. The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 46, wherein the sulfonic acid derivatized groups extend into the bulk of the interpenetrating or semi-interpenetrating polymer network for a distance of at least 1 mm. [Embodiment 48] 47. The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 46, wherein the sulfonic acid derivatized groups are present across more than 20% of the thickness of the interpenetrating or semi-interpenetrating polymer network. [Embodiment 49] 47. The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 46, wherein the sulfonic acid derivatized groups are present across more than 50% of the thickness of the interpenetrating or semi-interpenetrating polymer network. [Embodiment 50] 47. The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 46, wherein the sulfonic acid derivatized groups are present across greater than 75% of the thickness of the interpenetrating or semi-interpenetrating polymer network. [Embodiment 51] 47. The interpenetrating or semi-interpenetrating polymer network of embodiments 37 to 46, wherein the sulfonic acid derivatized groups are present throughout 100% of the thickness of the interpenetrating or semi-interpenetrating polymer network.

Claims

1. A packaged article comprising an orthopedic implant and a divalent cation-containing solution contained within a sterile package, The orthopedic implant comprises a crosslinked ionic polymer comprising sulfonic acid derivatized carboxylic acid groups; the sulfonic acid derivatized carboxylic acid groups are present on the surface of the crosslinked ionic polymer and extend from the surface into the bulk of the crosslinked ionic polymer a distance of at least 500 microns; the crosslinked ionic polymer has a thickness in the range of 10 mm or less; and The above packaged article, wherein the divalent cation-containing solution comprises 0.5 to 5.0 mM calcium ions and 0.2 to 1.5 mM magnesium ions.

2. 2. The packaged article of claim 1, wherein the sulfonic acid derivatized carboxylic acid group is an aminosulfonic acid derivatized carboxylic acid group.

3. The crosslinked ionic polymer is provided with a measurable amount of the formula (H 2 N) x R(SO 3 H) y 3. The packaged article of claim 2, comprising an aminosulfonic acid compound of the formula: or a salt thereof, wherein R is an organic moiety, x is a positive integer, and y is a positive integer.

4. 4. The packaged article of claim 3, wherein R is a hydrocarbon moiety.

5. 5. The packaged article of claim 4, wherein the hydrocarbon moiety is an alkane moiety, an alkene moiety, an alkyne moiety, an aromatic moiety, or a hydrocarbon moiety having a combination of two or more of alkane, alkene, alkyne, and aromatic substituents.

6. The hydrocarbon portion is C 1 ~C 12 5. The packaged article of claim 4, wherein the moiety is a hydrocarbon moiety.

7. The packaged article of claim 2, wherein the crosslinked ionic polymer comprises a measurable amount of an aminosulfonic acid compound selected from taurine and taurine derivatives.

8. 8. The packaged article of claim 7, wherein the crosslinked ionic polymer further comprises underivatized carboxylic acid groups.

9. 9. The packaged article of claim 8, wherein the underivatized carboxylic acid groups correspond to one or more of the following: underivatized acrylic acid polymerized monomer in an ionic polymer, underivatized methacrylic acid polymerized monomer in an ionic polymer, underivatized crotonic acid polymerized monomer in an ionic polymer, underivatized linoleic acid polymerized monomer in an ionic polymer, underivatized maleic acid polymerized monomer in an ionic polymer, and underivatized fumaric acid polymerized monomer in an ionic polymer; and the aminosulfonic acid derivatized carboxylic acid groups correspond to one or more of aminosulfonic acid derivatized acrylic acid polymerized monomer in an ionic polymer, aminosulfonic acid derivatized methacrylic acid polymerized monomer in an ionic polymer, aminosulfonic acid derivatized crotonic acid polymerized monomer in an ionic polymer, aminosulfonic acid derivatized linoleic acid polymerized monomer in an ionic polymer, aminosulfonic acid derivatized maleic acid polymerized monomer in an ionic polymer, and aminosulfonic acid derivatized fumaric acid polymerized monomer in an ionic polymer.

10. The packaged article of claim 1, wherein the crosslinked ionic polymer comprises a concentration gradient of sulfonic acid derivatized carboxylic acid groups.

11. 10. The packaged article of claim 1, wherein the sulfonic acid derivatized carboxylic acid groups extend into the bulk of the crosslinked ionic polymer a distance of at least 1 mm.

12. 10. The packaged article of claim 1, wherein the sulfonic acid derivatized carboxylic acid groups are present through greater than 20% of the thickness of the crosslinked ionic polymer.

13. 10. The packaged article of claim 1, wherein the sulfonic acid derivatized carboxylic acid groups are present through 100% of the thickness of the crosslinked ionic polymer.

14. 10. The packaged article of claim 1, wherein the concentration of sulfonic acid derivatized carboxylic acid groups is reduced by at least 10% from a point on the surface of the crosslinked ionic polymer to at least one point in the bulk of the crosslinked ionic polymer.

15. 10. The packaged article of claim 1, wherein the concentration of sulfonic acid derivatized carboxylic acid groups does not vary by more than + / - 10% between any two points in the crosslinked ionic polymer.

16. 9. The packaged article of claim 8, wherein the concentration of sulfonic acid derivatized carboxylic acid groups and the concentration of underivatized carboxylic acid groups do not vary by more than + / - 10% between any two points in the crosslinked ionic polymer.

17. The packaged article of claim 8, wherein the crosslinked ionic polymer comprises a gradient concentration of sulfonic acid derivatized carboxylic acid groups and a gradient concentration of said underivatized carboxylic acid groups.

18. 9. The packaged article of claim 8, wherein the concentration of sulfonic acid derivatized carboxylic acid groups decreases by at least 10% from a point on the surface of the crosslinked ionic polymer to at least one point in the bulk of the crosslinked ionic polymer and the concentration of underivatized carboxylic acid groups increases by at least 10% from a point on the surface of the crosslinked ionic polymer to at least one point in the bulk of the crosslinked ionic polymer.

19. 9. The packaged article of claim 8, wherein the molar ratio of sulfonic acid derivatized carboxylic acid groups to underivatized carboxylic acid groups is reduced by at least 10% from a point on the surface of the crosslinked ionic polymer to at least one point in the bulk of the crosslinked ionic polymer.

20. The packaged article of claim 1, wherein the crosslinked ionic polymer comprises an interpenetrating or semi-interpenetrating polymer network forming a molded article, the interpenetrating or semi-interpenetrating polymer network comprising a first polymer and a second polymer network comprising an ionic polymer.

21. 21. The packaged article of claim 20, wherein the first polymer is a hydrophobic polymer.

22. 21. The packaged article of claim 20, wherein the first polymer is a thermoplastic polymer.

23. The packaged article of claim 20, wherein the interpenetrating or semi-interpenetrating polymer network has a first and a second surface, the first surface having a composition corresponding to the first polymer, and the concentration of sulfonic acid derivatized carboxylic acid groups is greatest at the second surface and decreases to zero or substantially zero in the bulk of the interpenetrating or semi-interpenetrating polymer network.

24. The packaged article of claim 1, wherein the cross-linked ionic polymer is configured to repair or replace cartilage in a joint within the body.

25. 25. The packaged article of claim 24, wherein the joint in the body is selected from a knee joint, condyle, patella, tibial plateau, ankle joint, elbow joint, shoulder joint, finger joint, thumb joint, glenoid cavity, hip joint, intervertebral disc, facet joint, labrum, meniscus, metacarpal joint, metatarsal joint, toe joint, temporomandibular joint, and wrist joint (including portions thereof).

Citation Information

Patent Citations

  • Hydrophilic interpenetrating polymer network derived from hydrophobic polymers

    JP2011527377A

  • An implant having a calcium-containing surface, and a method for modifying the surface of an implant to impart calcium to the surface.

    JP2013537074A

  • Orthopedic implants with gradient polymer alloys

    JP2014506177A

  • PVA hydrogels having improved creep resistance, lubricity, and toughness

    US20100210752A1